Adsorption behaviour of tetracycline on fresh and aged Zn-modified biochar in the presence of copper: Insights into the synergistic effect and mechanism - Hua Deng; Song Lei; Shujia Chen; Xiaotong Zhou; Jiahui Fu; Pan Chen; Lening Hu; Anyu Li (Biomass and Bioenergy, 2026)

Hydrogen substitution regulating reaction pathways at active sites of amine-based deep eutectic solvents for enhancing CO2 absorption - Shaoyu Wang; Yueying Li; Haoran Pan; Hua Li; Xinhui Ma; Xingxing Chen; Jinxiao Dou; Jianglong Yu (Chemical Engineering Journal, 2026)

Thermal effects on aquifer storage and recovery in brackish aquifers - Hongkai Li; Zhilin Guo; Zidong Pan; Yang Zhan; Sichen Wan; Hua Zhong; Chunhui Lu; Chunmiao Zheng (Journal of Hydrology, 2026)

Spatiotemporal inequities in early-life ecological liveability and sleep health in preschool children - Yongzhou Liang; Hao Pan; Qiyan Chen; Huizhen Li; Xinyi Weng; Mengqiu Cao; Huiyu Zhou; Nahid Mohajeri; Lin Wang; Tianren Yang; Jing Hua (Environmental Pollution, 2026)

PFAS exposure is associated with retinal neurotoxicity in Chinese adolescents: Mechanistic insights from integrated toxicogenomic and in vitro analyses - Xing-Xuan Dong; Shi-Yi Gong; Yu-Hui Hu; Gang Liang; Hua Xu; Dan-Lin Li; Yun Zhao; Chen-Wei Pan (Environmental Pollution, 2026)

Deep removal of Cu-EDTA from saline wastewater via an ozonation-adsorption process: Salt-promoting effect and nanocomposite sequestration - Xin Li; Zhiting Li; Lu Lv; Weiming Zhang; Bingcai Pan; Ming Hua (Chemical Engineering Journal, 2026)

Entropy-defect synergy for dual luminescence mechanism in spinel: Time-resolved anti-counterfeiting and fingerprint visualization - Zemeng Pan; Shifa Wang; Jingyi Yang; Peilin Mo; Yanming Chen; Huajing Gao; Xianju Zhou; Dengfeng Li; Hua Yang; Huijun Zhang; Leiming Fang; Qingping Ding (Chemical Engineering Journal, 2026)

A new strategy to enhance the responsiveness of intelligent film to the freshness of chilled pork: UiO-66-TFA as a volatile amine-specific adsorption system - Jiayin Hou; Gege Su; Leyi Li; Xue Pan; Yiheng Deng; Wenhao Luo; Hongtao Lei; Hua Zheng; Zonglin Guo (Food Control, 2026)

Activity-guided discovery of antibiotic-transforming bacteria from environmental microbiomes using D-amino acid–assisted fluorescence-activated cell sorting - Yi Liu; Kai-Li Wang; Yu-Qi Hong; Ye Yuan; Hua Wang; Yi-Qun Chen; Sheng-Song Yu; Zi-Xuan Lu; Yuan Pan; Ting-Ting Zhu (Environmental Pollution, 2026)

Superphosphate-driven low-pH regime reduces greenhouse gas emissions during manure composting - Yuchen Yang; Huijie Li; Pan Wu; Shuang Peng; Qingqing Hua; Beibei Zhou; Yiming Wang; Xiangui Lin (Bioresource Technology, 2026)

ROMO1 loss in cholinergic neurons induces mitochondrial ultrastructural damage and ALS-like neuromuscular degeneration - Wei Nie; Zhiwen Jing; Linling Cheng; Lin-Lin Li; Yuxiao Bai; Fengli Xu; Sihan Li; Limei Lin; Xiaohui Dong; Liping Yu; Lei Cai; Bingxing Pan; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Deep eutectic solvent as dual roles for molecularly imprinted polymers: A green strategy for selective adsorption of Sulfamethoxazole - Hui Feng; Yuxin Li; Shaobo Zhang; Jiaxin Xu; Jieyu Xu; Hua Zou; Gang Pan (Journal of Hazardous Materials, 2026)

Electrostatic effect and spatial conformation regulating interfacial stability and digestion of shrimp myofibrillar protein-fish oil oleogel emulsions - Yanmo Pan; Yumin Niu; Shucheng Liu; Yuxuan Wu; Zhuoyan Li; Xueyan Cao; Zongyuan Han; Jun-Hua Shao; Hongwu Ji; Mouming Zhao (Food Chemistry, 2026)

Diagnosis of neurodegenerative diseases based on molecular imaging - Li Quan; Maoran Lang; Jiangtao Yue; Jiatao Zhu; Jinyao Xu; Kewei Wang; Hao Huang; Qinyong Song; Yingshi Zhao; Zhu Zhu; Chenqi Zhu; Bo Liu; et al. (Chemical Engineering Journal, 2026)

The effect of arbuscular mycorrhizal fungi on the physiological and biochemical functioning of the ornamental species Catalpa bungei against Meloidogyne incognita - Zhen-Hui Wang; Xue-Li Mou; Pan-Pan Meng; Gui-Hua Meng; Wei Chen; Xia-An Tang; Ke-Xu Xin; Yi Zhang; Chun-Yan Wang (European Journal of Plant Pathology, 2026)

Loss of lncRNA AK015322 increases sperm morphological abnormalities and impairs motility in mice - Qinran Zhu; Shiyu Pan; Xin Li; Chuangchuang An; Xinyu Yang; Li Hua; Lei Liu; Junpei Sun; Meng Liang; Ke Hu (Molecular and Cellular Biochemistry, 2026)

Genotypic features of Spinocerebellar Ataxia in Northern China: A Comparative Analysis with Southern China - Bin Chen; Songtao Niu; Xingao Wang; Yutin Ren; Fan Jian; Yuzhi Shi; Hongfei Tai; Hengheng Wang; Zhan Wang; Tao Cui; Wei Li; Hua Pan; et al. (The Cerebellum, 2026)

Pancancer pro-angiogenic atlas unravels tumor-educated pericyte-augmented anti-angiogenic resistance - Yongqiang Zheng; Hui Sun; Zhe Fu; Haojie Chen; Guangyao Cai; Xin Huang; Yi-Qian Pan; Kai Yu; Ping Chen; Zhuoran Liang; Junteng Li; Jiamin Hu; et al. (Science Bulletin, 2026)

Environmental cadmium drives placental senescence and fetal growth restriction via activating CLPP-dependent mitochondrial stress - Rui Pan; Jin Zhang; Lan-Lan Wu; Cheng-Fang Sun; Xin-Xin Zhang; Yu-Xi Wu; Xu-Ai Yin; Ye-Xin Luo; Si-Ting Liu; Zi-Jian Bao; Wei Chang; Ling-Li Zhao; et al. (Journal of Hazardous Materials, 2026)

Environmental Impacts of Selenium in Chinese Soil on Traditional Chinese Medicinal Plants and Human Health - Ying Pan; Waqar Ali; Muhammad Shafeeque; Kang Mao; Wei Li; Hua Zhang (Water, Air, & Soil Pollution, 2026)

Mitophagy activation for jawbone radiation injury therapy via angiogenesis/osteogenesis-active nanozymes - Tianxiao Wang; Weihua Shao; Ting Zhou; Yuchao Li; Ran Qin; Ziyu Chen; Jikang Cao; Xinyu Hu; Jingxuan Cang; Chang Sun; Yuli Wang; Huijun Jiang; et al. (Science China Life Sciences, 2026)

Non-thermal plasma-induced NH3 selective oxidation to NH4NO3 - Kai Li; Yunhe Xing; Yuxuan Ding; Baigen Wang; Weiqiang Shen; Jie Guo; Chong Wang; Yuzhen Jin; Liancheng Zhang; Hua Pan; Fada Feng; Xuming Zhang (Journal of Environmental Chemical Engineering, 2026)

Transparent superhydrophobic high-emissivity coatings for synergistic self-cleaning and passive cooling of photovoltaics - Li Wan; Yan Yang; Chao-Hua Xue; Xiao-Jing Guo; Pan Lu; Jing-Jing Peng (Chemical Engineering Journal, 2026)

Solid-anode electrolysis of Cu2Te in a ChCl–urea deep eutectic solvent for minimal-electron-transfer recovery of copper and tellurium - Jihua Li; Qihang Zhang; Zihan Zhang; Haoyi Pan; Shiwei He; Hui Kong; Zhongsheng Hua; Zhuo Zhao (Chemical Engineering Journal, 2026)

Synergistic optimization of power matching and layout for fracturing–drilling equipment in extremely limited spaces via a hybrid GA–SA algorithm - Lei Zhang; Guangyu Yang; Bo Pan; Hua Liu; Yichao Li; Fulong Sun; Yunxiang Wang; Yue Sun; Huale Geng; Dongsheng Jiang (Computational Geosciences, 2026)
Fracturing operations for thick-roof control in underground coal mines—especially at the Hetaoyu Coal Mine in the Ordos Basin—are frequently restricted to extremely constrained workspaces (approximately 5,460 m $$^2$$ 2 ). Under such conditions, conventional experience-based planning often fails to simultaneously satisfy safety clearances, power-demand matching, and workflow efficiency. This paper proposes a synergistic power–layout optimization framework for fracturing–drilling equipment in minimal-area sites. First, a power–area coupling model is established to map functional power requirements to explicit spatial–geometric constraints. Second, a multi-objective optimization model is formulated to maximize site utilization while minimizing logistics costs and the center-of-mass (CoM) offset to enhance foundation stability. Third, a hybrid Genetic Algorithm–Simulated Annealing (GA–SA) algorithm is developed to solve the resulting nonlinear and highly constrained layout problem. Results show that the proposed GA–SA approach converges 31.7% faster than a standard GA. The optimized layout achieves 85.3% site utilization, limits the CoM offset to 1.23 m, and incorporates a dedicated fracturing operation lane to support high-pressure pumping operations. The proposed framework provides a quantitative and practical basis for safe, efficient drilling–fracturing integration in geotechnically sensitive sites with severely limited available area.

A new mechanism for magnetite formation in loess - Yifan Hua; Guiping Ren; Hua Li; Qijun Wang; John A. Tarduno; Junfeng Huang; Chengying Liu; Yiping Yang; Ronghua Wang; Xueqin Yang; Xiaohua Han; Yongxin Pan; et al. (Science Bulletin, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

An evaluation of Tetrastigma hemsleyanum leaves: Digestion, absorption and anti-inflammatory effects via an in vitro digestion-Caco-2-HT-29 model - Lihua Xiao; Xin Bi; Yanhua Xue; Feng Pan; Hua Zhang; Li Jiang; Yong Sun (Food Bioscience, 2026)

Slow-release fertilizers applied in conjunction with manure enhanced soil quality and rice grain yield by regulating labile nutrient pools, soil enzyme activities, and soil structure - Qing Shan Xu; Yu Lian Yan; Hang Feng Wang; Shang Pan Li; Chun Xin Chi; Ya Li Kong; Wen Hao Tian; Xiao Chuang Cao; Lian Feng Zhu; Qiao Ling Li; Jing Wang Li; Jun Hua Zhang; et al. (Field Crops Research, 2026)

Research progress in atmospheric haze chemistry: Formation mechanism of air pollution complex and control technologies - Qingxin Ma; Peng Zhang; Tianzeng Chen; Hao Li; Yonghong Wang; Jun Liu; Pengfei Liu; Yujing Mu; Jingjing Liu; Zhi Liu; Guangyan Xu; Yulong Shan; et al. (Journal of Environmental Sciences, 2026)

Effects of carbonization temperature on the synthesis and antibacterial properties of honeysuckle carbon dots: Application in extending pork shelf life - Leyi Li; Gege Su; Yiheng Deng; Xue Pan; Jiayin Hou; Wenhao Luo; Hua Zheng; Hongtao Lei; Xiangzhen Ge; Zonglin Guo (Food Packaging and Shelf Life, 2026)

High-performance composite solid electrolyte with elevated ionic liquid and high-dielectric high-entropy oxide in poly(vinylidene fluoride-co-hexafluoropropylene) for advanced lithium-ion batteries - Wen-Hsuan Lu; Yen-Shuo Huang; Yen-Lin Chen; Yi-Hsuan Tseng; Jue-Hua Pan; You-Yi Li; Ying-Da Luo; Chun-Han Kuo; Chih-Ping Tan; Ruey-An Doong; Ho-Hsiu Chou; Ai-Yin Wang; et al. (Chemical Engineering Journal, 2026)

Synergistic co-preintercalation of nickel and aluminum ions into vanadium oxide hydrate as positive electrode material in ultrahigh-rate and high-capacity aqueous zinc-ion batteries - Hung-Lin Chen; Tsung-Yi Chen; En-Hao Li; Yen-Lin Chen; Wen-Hsuan Lu; Hsu-Chen Cheng; Shu-Yu Chen; Jue-Hua Pan; Hsiang-Jung Chen; Syuan-Cen Lin; Ruey-An Doong; Sanna Gull; et al. (Chemical Engineering Journal, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Association between atorvastatin and sarcopenia: a study based on NHANES and FAERS databases - Hao Zhang; Ping Zhang; Xi Luo; Li Pan Zhao; Hua Huang; Qi Hong Ou (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Phytochemistry and biological activities of genus Chloranthus : a review - Shuping Wang; Juan Pan; Yuxuan Wang; Lixia Chen; Hua Li; Yan Liu (Natural Product Research, 2026)

Efficient decomplexation of Cu(II) complexes and Cu(II) recovery via one-step Fenton-like oxidation/adsorption processes mediated by nanoconfined hydrous Co-Zr oxides - Xin Li; Xuewei Song; Lu Lv; Weiming Zhang; Bingcai Pan; Ming Hua (Water Research, 2026)

Analyzing the key drivers of pollutant transport in semi-enclosed bays: Insights based on numerical model and interpretable machine learning - Chenxiao Wang; Lei Hua; Aiju You; Xiang Li; Xinwen Li; Laiyu Jin; Hongzhe Pan; Yaning Wang; Haibin Yan; Yiping Li (Journal of Environmental Management, 2026)

Real-time monitoring of monocyclic non-chlorinated aromatic compounds in incineration flue gas by photoionization time-of-flight mass spectrometer for dioxin prediction - Meihui Ren; Lifang Gong; Yi Yu; Guangzhao Guo; Haijun Zhang; Hong Yao; Xiaodong Zeng; Zhuo Pan; Wei Huang; Haiyang Li; Jichun Jiang; Lei Hua (Fuel, 2026)

Anti-diabetic properties of yellowfin tuna protein hydrolysates and identification and screening of novel anti-diabetic peptides against α-amylase and DPP-IV - Xiangtan Zhao; Peng Wan; Deke Chen; Bingna Cai; Hua Chen; Jun Li; Si Li; Ailing Duan; Ru Li; Si Zhang; Jianyu Pan (Food Chemistry, 2026)

Deciphering functional adaptability of microalgal-bacterial granular sludge under salicylic acid stress - Hua Liang; Wen Pan; Shulian Wang; Anjie Li; Shenbin Cao; Bin Ji (Bioresource Technology, 2026)

Systematic investigation, expression analysis of TCP transcription factors in eggplant and functional characterization of SmTCP3 gene involved in response to drought stress - Fa-xiang Wan; Yu Zheng; Rong-rong Li; Ying-fan Zhang; Hua-ju Zheng; Ji-qing Li; Yi-min Jiang; Jia-rui Yang; Bo Qi; Jun Gao; Ya-nan Chen; Yu Pan (Genetic Resources and Crop Evolution, 2026)

Overlooked Roles of Pharmaceutical Metabolic Products in Stimulating Microbial Metabolism and Antibiotic Resistance Gene Dissemination of Anaerobic Sludge - Jing Wu; Dan Sun; Yuan Pan; Dong‐Feng Liu; Hui Zhang; Jun‐Hua Zhou; Tong Gao; Jie Wu; Ru‐Li He; Yin‐Guang Chen; Wen‐Wei Li (Environmental Microbiology, 2026)
The roles of non‐antibiotic pharmaceuticals in shaping the dissemination behaviours of antibiotic resistance genes (ARGs) in wastewater treatment systems remain poorly understood, and the influences of their transformation products have been overlooked. Here, we unveil more profound impacts of the metformin (MET) biotransformation product than the parent pollutant on the microbial community structure and ARG propagation of wastewater anaerobic sludge. The exposure to MET and its metabolic products guanylurea (GUA) at environmentally relevant concentrations both raised the methane production and resulted in up to 52.5% higher sludge ARGs abundance relative to the unexposed control. Especially, the GUA group showed up to 188‐fold upregulation in several ARGs including bcrA , PmrF , acrB and mexF , enabled 3218‐fold enrichment of plasmids from several bacteria. The underlying mechanisms were elucidated by integrated metagenomics, molecular dynamics simulations, and metabolic profiling analyses. MET and GUA were found to trigger coordinated cellular responses including disrupted glycerophospholipid metabolism, increased membrane permeability and broad metabolic reprogramming, which collectively boosted the ARGs dissemination. Overall, this work establishes a mechanistic link between micropollutant‐induced microbial stress and ARGs propagation in anaerobic sludge, and advocates for re‐evaluating the environmental risks of non‐antibiotic pharmaceuticals and integrating resistance control into wastewater management framework.

Performance of heavy metals in the intertidal zone surface sediments of the Yellow River Estuary under water-sediment regulation scheme - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Jun Ma; Feng Min Pan; Jian Wei Xing; Chen Long Feng; De Tong Tian; Zhi Bo Wang; Rui Wang (Marine Pollution Bulletin, 2025)

Interfacial Schottky junction-enhanced charge separation in BC/CoFe2O4/nZVI for photocatalytic removal of complex pollutants via peroxymonosulfate activation - Ye Yang; Shuang Liu; Maolei Li; Jiaxiang Li; Mihail-Simion Beldean-Galea; Hua Pan; Qingquan Xue; Shengdao Shan; Xiaofeng Shen (Chemical Engineering Journal, 2025)

Machine learning-aided design of adapted water treatment adsorbents: Advances, challenges, and opportunities - Ling Yuan; Sheng Li; Yujia Ma; Han Zhang; Chen Chen; Weiming Zhang; Yanyang Zhang; Ming Hua; Lu Lv; Bingcai Pan (Chemical Engineering Journal, 2025)

Evaluation of Feeding Effect of a New Artificial Diet on Chilo sacchariphagus and Chilo infuscatellus (Lepidoptera: Crambidae), Two Major Stalk Borers on Sugarcane in China - Ji-li Wei; Yong-lin Ma; Cheng-hua Huang; Feng-ying Wang; Qiao-xian Wei; Liu-feng Li; Ren-zhao Liao; Fu Lv; Xue-hong Pan; Xian-kun Shang (Sugar Tech, 2025)

Hypoxia-induced S100A10 promotes glioblastoma malignancy and chemoresistance by activating PI3K-AKT signaling pathway - Qingqing Yang; Yunlan Xi; Xuewei Huang; Wenzhe An; Cuiyun Sun; Qian Wang; Dan Hua; Wenjun Luo; Cuijuan Shi; Hongli Pan; Zhendong Jiang; Bingkun Wang; et al. (Functional & Integrative Genomics, 2025)

Interactions between raw dark tea chemistry and dominant fungi shape Hei brick tea quality - Yating Guo; Haijing Cui; Xinxin Wang; Haowei Guo; Xinyu Feng; Anran Yan; Yani Pan; Lixin He; Liping Liu; Kexin Zhang; Hua Fang; Hesham R. El-Seedi; et al. (International Journal of Food Microbiology, 2025)

Development of chondroitin sulfate-modified quinoa protein isolate-dihydromyricetin composite nanoparticles: Focus on naringenin delivery, cell cytoprotective ability and anti-inflammatory effects - Ying-Ying Chen; Xue-Ying Li; Qiang-Ming Li; Li-Hua Pan; Jian-Ping Luo; Xue-Qiang Zha (Food Chemistry, 2025)

Fabricating MOF-derived Co N C@Fe N C phase change nanocomposites by layered self-assembly strategy for energy storage, photothermal conversion, and microwave absorption - Sijia Liu; Xinman Li; Jie Zhang; Chunshuai Cao; Dan Liu; Shiguang Pan; Aijing Ma; Hua Yuan; Hu Li; Jianzhou Gui (Chemical Engineering Journal, 2025)

The potential of nanoscale zero-valent iron as an additive for swine slurry and pulverized wolfberry branch co-composting from the perspective of nitrogen retention and greenhouse gas emissions - Xu Yang; Miaoqu Wang; Cong Shao; Yang Wang; Kuok Ho Daniel Tang; Bowen Wang; Hua Li; Ronghua Li; Junting Pan (Journal of Environmental Chemical Engineering, 2025)

Virtual screening and molecular mechanism of novel anti-benign prostatic hyperplasia peptides from Syngnathus schlegeli - Ailing Duan; Xiangxi Yi; Xiangtan Zhao; Si Li; Xinjian Qu; Geng Qin; Qiang Lin; Hua Chen; Peng Wan; Deke Chen; Xin Chen; Weimao Zhong; et al. (Food Research International, 2025)

Purification, identification, and mechanism of action of novel antioxidant peptides from quinoa (Chenopodium quinoa wild.) protein hydrolysate - Huan-Huan Xiao; Xue-Ying Li; Ying-Ying Chen; Jin-Xiang Zhou; Ting Zhang; Qiang-Ming Li; Li-Hua Pan; Jian-Ping Luo; Xue-Qiang Zha (Food Chemistry, 2025)

Saleucanes A-J, structurally diverse neo-clerodane diterpenoids from Salvia leucantha with anti-neuroinflammatory activity via TLR4/MYD88/NF-κB pathway - Fen-Cong Pan; Han-Fei Liu; Xiao-Die Shu; Xiao-Qiao Yang; Hua-Yong Lou; Wei-Dong Pan; Ni Zhang; Jin-Yu Li (Phytochemistry, 2025)

Response of Litopenaeus vannamei to dietary Isothiocyanate: Growth, biochemistry, immunity and gene expression related to hepatopancreas and intestinal health - Chen Chen; Mengling Nie; Xinghui Cai; Ying Hang; Aike Li; Lin Qiao; Peng Kang; Qianqian Wang; Yunchao Pan; Xueming Hua (Fish & Shellfish Immunology, 2025)

Design of 2D/2D Pt SA-MoS2/ZnIn2S4 photocatalysts for boosting hydrogen production - Xue-Lu Chen; Miao Ni; Yan-Ru Li; Yi-An Pan; Chen Chi; Yi Yang; Si-Meng Li; Sudip Biswas; Yi-Bai Sun; Xing-Hua Xia (Chemical Engineering Journal, 2025)

Ground Motion Simulation Via Generative Adversarial Network - Kai Chen; Hua Pan; Meng Zhang; Zhi-Heng Li (Applied Geophysics, 2025)

Experimental research on the suppression of hydrogen deflagration by flame-retardant composite ultrafine dry powder fire extinguishing agents containing aluminum hydroxide - Xinxin Guo; Yuhang Chen; Sijia Xue; Zhilei Wang; Jingxian Li; Xuhai Pan; Min Hua; Juncheng Jiang (Process Safety and Environmental Protection, 2025)

Development of a novel LBL@DHBA/Cu-MOF coating on titanium implants to accelerate early osseointegration by promoting neural-vascular-bone coupling regeneration - Peng Hua; Xiaoyi Pan; Jiming Liu; Xuemei Chen; Manjuan Li; Yan Guo; Xuan Li; Pengyuan Leng; Guoyong Fan; Mengjiao Zheng; Kai Yu; Pingping Ma; et al. (Chemical Engineering Journal, 2025)

Advancements in chain elongation technology: Transforming lactic acid into caproic acid for sustainable biochemical production - Minyu Suo; Lingxiu Liu; Hongye Fan; Nan Li; Hua Pan; Dzmitry Hrynsphan; Savitskaya Tatsiana; Raúl Robles-Iglesias; Zeyu Wang; Jun Chen (Bioresource Technology, 2025)

Deep Placement of Fertilizer and Straw Incorporation Improved Grain Yield and 2-acetyl-1-pyrroline (2-AP) of Fragrant Rice - Meiying Liu; Zhenzhen He; Pipeng Xing; Yizhu Wu; Xiaojuan Pu; Haidong Liu; Yingqi Li; Hua Tian; Zhaowen Mo; Meiyang Duan; Xiangru Tang; Shenggang Pan (Journal of Soil Science and Plant Nutrition, 2025)

Tracking of single virus: Dual fluorescent labeling of pseudorabies virus for observing entry and replication in the N2a cells - Mingzhi Li; Li Pan; Caoyuan Ma; Hongxia Wu; Guangtao Xiang; Lian-Feng Li; Tao Wang; Rui Luo; Yongfeng Li; Di Liu; Huanjie Zhai; Moon Assad; et al. (Veterinary Microbiology, 2025)

Experimental demonstration of reconstructing quantum states with generative models - Xuegang Li; Wenjie Jiang; Ziyue Hua; Weiting Wang; Xiaoxuan Pan; Weizhou Cai; Zhide Lu; Jiaxiu Han; Rebing Wu; Chang-Ling Zou; Dong-Ling Deng; Luyan Sun (Science Bulletin, 2025)

Immunomagnetic metal-organic frameworks based coupling-free and extraction-free sensitive detection of aflatoxin B1 in peanut oils - Zhihong Xuan; Jin Ye; Baoxia Ni; Hua Cui; Li Li; Jinnan Chen; Yao Qin; Quan Pan; Hongmei Liu; Songxue Wang (Food Chemistry, 2025)

Thermosensitive poly (NVCL-co-GelMA) nanogels as a delivery platform for rectal administration of 5-ASA in ulcerative colitis - Rongjiao Sun; Limei Zhu; Xianzhu You; Rong Chen; Jiante Li; Rongrong Pan; Yueqi Jin; Hua Zhou; Ying Tan; Jiajia Dong; Wanle Hu (Chemical Engineering Journal, 2025)

Enhanced methanogenesis of wastewater anaerobic digestion by nanoscale zero-valent iron: Mechanism on intracellular energy conservation and amino acid metabolism - Jibin Li; Lingyun Zhou; Jinhao Zhao; Weiming Zhang; Bingcai Pan; Ming Hua (Bioresource Technology, 2025)

Forest litter decomposition stimulates heterotrophic nitrogen fixation by driving diazotrophic community interactions - Chang Pan; Shuikuan Bei; Zhe Hua; Mengtian Zhou; Zichen Wang; Ruoxian Fu; Xiaogang Li (Biology and Fertility of Soils, 2025)

Anti-ferroptosis effects of undescribed abietane diterpenoids from Prunella vulgaris subsp . hispida (Benth.) Hultén - Heng-Li Yan; Xiao-Qiao Yang; Han-Fei Liu; Fen-Cong Pan; Jin-Yu Li; Wei-Dong Pan; Ni Zhang; Hua-Yong Lou; Chao Sun (Natural Product Research, 2025)

Transcriptome analysis of Ipomoea cairica algicidal mechanism against Phaeocystis globosa - Dayong Liang; Huanxin Li; Yuxuan Pan; Zihan Liu; Hua Xiang (Frontiers in Marine Science, 2025)
Phaeocystis globosa is a globally distributed harmful algal bloom species that causes severe damage to local environments and economies. The use of the invasive plant Ipomoea cairica as an algaecide for P. globosa is an environmentally friendly management strategy. Although previous studies have found that I. cairica extracts can effectively inhibit P. globosa growth, the molecular mechanism of cellular response to this algaecide remains unclear. Therefore, transcriptome differences between 24 and 48 h after treatment with I. cairica extracts were investigated to explore the P. globosa gene expression changes in response to the algaecide. In this study, control groups were treated with sterile seawater, while experimental groups were exposed to I. cairica extracts (final concentration of 1%). The results of physiological experiments showed no difference in the number of solitary cells and colonies at 24 h, but significant decreases at 48 h. Transcriptomic data also showed significant differences in differentially expressed genes (DEGs) at 24 and 48 h. DEGs were mainly upregulated at 24 h and downregulated at 48 h. Mitogen-activated protein kinase (MAPK) and phosphatidylinositol (PI) signaling pathways that respond stress in the external environment were activated throughout the response process. Genes related to the antioxidant enzyme system and autophagy were upregulated at 24 h, which may contribute to the stress response mechanisms of P. globosa. Downregulation of photosynthesis-related genes leading to inhibition of the photosynthetic system and thus accelerating the accumulation of reactive oxygen species (ROS) may be responsible for the eventual cell death. In addition, 411 known compounds were identified usingultra-high-performance liquid chromatography (UHPLC). Unfortunately, apigenin-7-O-glucoside, a flavonoid, did not have a significant inhibitory effect on P. globosa. This study highlights the mechanism of the toxic effect of I. cairica extracts on P. globosa and provides a theoretical basis for the development of an algaecide targeting P. globosa.

Synergistic generation of ROS via covalent organic frameworks with excellent energy transfer and charge transfer characteristics for phenolic pollutants treatment - Long Zhang; Liujun Yang; Wanyu Wei; Shaoshuo Wang; Yicheng Pan; Yuhan Gu; Liren Gu; Chen Yu; Hua Li; Jianmei Lu (Journal of Environmental Chemical Engineering, 2025)

Plasma-enhanced low-temperature SCO of NH3 over Cu-Mn/SAPO-34 catalyst under oxygen-rich conditions - Kai Li; Yuxuan Ding; Fada Feng; Weiqiang Shen; Yuzhen Jin; Liancheng Zhang; Zhiqiang Lu; Dandan Wang; Hua Pan; Xuming Zhang (Chemical Engineering Journal, 2025)

Integrated Pest Management of Sugarcane Insect Pests in China: Current Status and Future Prospects - Xian-Kun Shang; Ji-Li Wei; Wei Liu; Amin Nikpay; Xue-Hong Pan; Cheng-Hua Huang (Sugar Tech, 2025)

Numerical solution of loose earth pressure in tunnels considering elliptical slip surface and soil arching effect - Ming Ma; Mingdong Li; Xiusong Shi; Yaosen Pan; Changyu Yang; Hua Ren (Tunnelling and Underground Space Technology, 2025)

Pathogenic Aeromonas veronii with the cheZ-mshK-aerA triple-gene mutant is attenuated and exhibits a potential candidate as a live attenuated vaccine - Jiahui Lu; Jinming Wei; Kemei Liu; Detao Li; Ziyang Li; Yongyao Yu; Hua Ye; Yun Li; Hao Xu; Xiaoyi Pan; Ronghua Wu (Fish & Shellfish Immunology, 2025)

scCrab: A Reference-Guided Cancer Cell Identification Method based on Bayesian Neural Networks - Heyang Hua; Wenxin Long; Yan Pan; Siyu Li; Jianyu Zhou; Haixin Wang; Shengquan Chen (Interdisciplinary Sciences: Computational Life Sciences, 2025)

Integrating multi-virion aerosols into the Wells–Riley equation with a focus on short-range exposure - Yuguo Li; Wei Jia; Pan Cheng; Ao Li; Hua Qian (Building and Environment, 2025)

OCTN2 expression and function in the Sertoli cells of testes from patients with non-obstructive azoospermia - Dong Li; Nan Jiang; Minjia Pan; Linzi Ma; Yunchong Huang; Xiaoheng Xu; Xinyan Yang; Yongtong Zhu; Hua Shi; Shan-Chao Zhao (Journal of Molecular Histology, 2025)

Corrigendum to “Meliasanines A–L, tirucallane-type triterpenoids from Melia toosendan with anti-inflammatory properties via NF-κB signaling pathway” [Phytochemistry 225 (2024) 114192]> - Li-Li Shao; Kai-Qin Lin; Han-Fei Liu; Zhi-Yao Li; Ni Zhang; Chao Chen; Wei-Dong Pan; Hua-Yong Lou; Jin-Yu Li (Phytochemistry, 2025)

Simultaneous effects of nanoscale zero-valent iron on wastewater decontamination and energy generation: Mechanisms of sulfamethoxazole degradation and methanogenesis - Lingyun Zhou; Jibin Li; Xingcheng Lu; Weiming Zhang; Bingcai Pan; Ming Hua (Journal of Hazardous Materials, 2025)

Effects of ozonation-enhanced coagulation on effluent organic matter and disinfection byproducts - Yufeng Liao; Leyi Wang; Yechao Tian; Jun Li; Qing Zhou; Aimin Li; Ming Hua; Yang Pan (Journal of Cleaner Production, 2025)

The beeswax-based fish oil oleogels adjusting the stabilization mechanism and lipid digestion of bi-layer emulsions: Spatial conformation and molecular interaction - Yanmo Pan; Shucheng Liu; Zongyuan Han; Huishan Li; Haoyan Lai; Jun-Hua Shao; Naiyong Xiao; Wen Xia (Food Hydrocolloids, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

A learning-based memetic algorithm for a cooperative task allocation problem of multiple unmanned aerial vehicles in smart agriculture - Teng-Yu Chen; Zhong-Hua Miao; Wei-Min Li; Quan-Ke Pan (Swarm and Evolutionary Computation, 2024)

Aggravation of Cd availability in the plastisphere of paddy soil - Ningyuan Zhu; Quanbo Yu; Li Tang; Rongxin Xie; Li Hua; Jing Wang; Jun Xing; Xia Pan; Eldon R. Rene; Yimin Wang (Science of The Total Environment, 2024)

Ameliorative effects of Trichosanthes kirilowii Maxim. seed oil on hyperlipidemia rats associated with the regulation of gut microbiology and metabolomics - Weili Chen; Zhangbao Zhou; Ruida Qi; Jun Zhou; Huiying Liang; Pinxi Huang; Zebin Zou; Ling Dong; Hua Li; Bing Du; Pan Li (Food Research International, 2024)

Long-term and multiscale assessment of methanogenesis enhancement mechanisms in magnetite nanoparticle-mediated anaerobic digestion reactor - Jibin Li; Desheng Sun; Siqi Wu; Wenlan Yang; Lei Xiong; Weiming Zhang; Ming Hua; Bingcai Pan (Environmental Research, 2024)

Integrated DNA methylation analysis of peripheral blood from asbestos exposed populations and patients with malignant mesothelioma reveals novel methylation driver genes of diagnostic and prognostic relevance - Lingfang Feng; Tao Li; Biao Xu; Jing Huang; Hailing Xia; Zhaoqiang Jiang; Junfei Chen; Simiao Pan; Xing Zhang; Hua Jiang; Jianlin Lou (Environmental Pollution, 2024)

Bioaccessibility and bioavailability assessment of cadmium in rice: In vitro simulators with/without gut microbiota and validation through in vivo mouse and human data - Fei-Fei Xu; Ying-Si Chen; Xiu-Qin Lin; Ai-Hua Zhong; Min Zhao; Yue-Qi Li; Zi-Yin Li; Yue-Fei Lai; Jia Song; Jia-Liang Pan; Zhan-Fan Cai; Xu-Xia Liang; et al. (Science of The Total Environment, 2024)

maxPIE: An innovative high throughput approach to enhance pathogen inactivation practices - Yundi Yin; Guifen Xiang; Yunlong Pan; Liu He; Haixia Xu; Wen-Hua Wei; Ling Li; Zhong Liu (Science of The Total Environment, 2024)

Dual decoration of quinoa protein isolate by different dietary polyphenols with covalent and noncovalent approaches: Structure characterization, conformational changes and functional properties - Ying-Ying Chen; Xue-Ying Li; Qiang-Ming Li; Li-Hua Pan; Jian-Ping Luo; Xue-Qiang Zha (Food Hydrocolloids, 2024)

Enhanced anaerobic digestion for energy recovery from brewery wastewater employing nano zero-valent iron loaded biochar prepared by residual sludge - Jibin Li; Siqi Wu; Weiming Zhang; Bingcai Pan; Ming Hua (Chemical Engineering Journal, 2024)

Anti-adipogenesis and anti-obesity potential of alliin mediated by modulating glycolipid metabolism via activating PPARγ signaling - Ming-Yan Yang; Yu-Jing Liu; Mei-Hua Zheng; Tao Pan; Zhen-Yuan Li; Bai-Fang Gong; Hua-Ying Fan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Optimizing Nitrogen Fertilization Managements Under Mechanical Deep Placement for Raising Rice Grain Yield - Qiankun Li; Zheng Zhang; Haidong Liu; Yizhu Wu; Meiying Liu; Zaiman Wang; Hua Tian; Xiaojuan Pu; Shenggang Pan (Journal of Plant Growth Regulation, 2024)

Short-term usage of proton pump inhibitors during admission was associated with increased risk of rehospitalization in critically ill patients with myocardial infarction: a cohort study - Jia-De Zhu; Li-Juan Yang; Jian-Nan Zhao; Ping Wang; Yi-Hua Li; Xue-Sha Zhang; Jian-Mei Pan; Meng-Han Jiang; Hai-Ying Yang; Sun-Jun Yin; Gong-Hao He (European Journal of Clinical Pharmacology, 2024)

Testosterone-promoting effects of Trichosanthes kirilowii-derived peptides on TM3 cells - Zhilin He; Dong Peng; Jieyu Zeng; Wanying Liang; Xinqi Li; Junyi Chen; Pan Li; Bing Du; Hua Li (Food Bioscience, 2024)

Meliasanines A–L, tirucallane-type triterpenoids from Melia toosendan with anti-inflammatory properties via NF-κB signaling pathway - Li-Li Shao; Kai-Qin Lin; Han-Fei Liu; Zhi-Yao Li; Ni Zhang; Chao Chen; Wei-Dong Pan; Hua-Yong Lou; Jin-Yu Li (Phytochemistry, 2024)

Effect of temperature on the development, reproduction and survival of Tetramoera schistaceana (Lepidoptera: Tortricidae) - Xue-Hong Pan; Ji-Li Wei; Xian-Kun Shang; Cheng-Hua Huang (Journal of Asia-Pacific Entomology, 2024)

Encapsulation of lycopene in Pickering emulsion stabilized by complexes of whey protein isolate fibrils and sodium alginate: Physicochemical property, structural characterization and in vitro digestion property - Qiaomei Zhu; Yihua Qiu; Lujia Zhang; Wenjing Lu; Yijun Pan; Xuanbo Liu; Zhenjing Li; Hua Yang (Food Research International, 2024)

Development and validation of individualized tacrolimus dosing software for Chinese pediatric liver transplantation patients: a population pharmacokinetic approach - Siyu Yang; Jian Wei; Xueqiang Pan; Ze Li; Xuanling Zhang; Zhe Li; Xianzhe Dong; Zixin Hua; Xingang Li (European Journal of Clinical Pharmacology, 2024)

Effect of gas saturation on P-wave velocity in tight sandstone - Bao-Zhi Pan; Wei-Yi Zhou; Yu-Hang Guo; Chun-Hui Fang; Li-Hua Zhang (Applied Geophysics, 2024)

Co-assembly of quinoa protein isolate and shellac as nano-vehicles for naringenin: Characterization, formation mechanism, release behavior and cellular uptake - Ying-Ying Chen; Qiang-Ming Li; Li-Hua Pan; Jian-Ping Luo; Xue-Ying Li; Xue-Qiang Zha (Food Hydrocolloids, 2024)

Research on the Energy Constitutive Model and Static Load Anchorage Characteristics of a Novel Mace-Type Energy Release Bolt - Huaibin Li; Weipeng Pan; Yunmin Wang; Xingdong Zhao; Xinzhu Hua; Bibo Dai (Geotechnical and Geological Engineering, 2024)

Correction to: Association of sudden sensorineural hearing loss with meteorological factors: a time series study in Hefei, China, and a literature review - Xiao‑Bo Li; Yan‑Xun Han; Zi‑Yue Fu; Yu‑Chen Zhang; Min Fan; Shu‑Jia Sang; Xi‑Xi Chen; Bing‑Yu Liang; Yu‑Chen Liu; Peng‑Cheng Lu; Hua‑Wei Li; Hai‑Feng Pan; et al. (Environmental Science and Pollution Research, 2024)

Reverse loading of inert Al2O3 onto active iron oxide for improved H2O2 activation and pollutant degradation - Chunli Song; Tian Xu; Jiuhe Bu; Hongchao Li; Xuan Zhang; Xiaodong Wang; Yuanqing Bu; Ming Hua; Bingcai Pan; Jieshu Qian (Chemical Engineering Journal, 2024)

Association of sudden sensorineural hearing loss with meteorological factors: a time series study in Hefei, China, and a literature review - Xiao-Bo Li; Yan-Xun Han; Zi-Yue Fu; Yu-Chen Zhang; Min Fan; Shu-Jia Sang; Xi-Xi Chen; Bing-Yu Liang; Yu-Chen Liu; Peng-Cheng Lu; Hua-Wei Li; Hai-Feng Pan; et al. (Environmental Science and Pollution Research, 2024)
Air pollution can cause disease and has become a major global environmental problem. It is currently believed that air pollution may be related to the progression of SSNHL. As a rapidly developing city in recent years, Hefei has serious air pollution. In order to explore the correlation between meteorological variables and SSNHL admissions, we conducted this study. This study investigated the short-term associations between SSNHL patients admitted to the hospital and Hefei climatic variables. The daily data on SSNHL-related hospital admissions and meteorological variables containing mean temperature (T-mean; °C), diurnal temperature range (DTR; °C), atmospheric pressure (AP; Hp), and relative humidity (RH; %), from 2014 to 2021 (2558 days), were collected. A time-series analysis integrating distributed lag non-linear models and generalized linear models was used. PubMed, Embase, Cochrane Library, and Web of Science databases were searched. Literature published up to August 2023 was reviewed to explore the potential impact mechanisms of meteorological factors on SSNHL. The mechanisms were determined in detail, focusing on wind speed, air pressure, temperature, humidity, and air pollutants. Using a median of 50.00% as a baseline, the effect of exceedingly low T-mean in the single-day hysteresis effect model began at a lag of 8 days (RR = 1.032, 95% CI: 1.001 ~ 1.064). High DTR affected the admission rate for SSNHL on lag 0 day. The significance of the effect was the greatest on that day (RR = 1.054, 95% CI: 1.007 ~ 1.104) and then gradually decreased. High and exceedingly high RH affected the admission rate SSNHL on lag 0 day, and these effects lasted for 8 and 7 days, respectively. There were significant associations between all grades of AP and SSNHL. This is the first study to assess the effect of meteorological variables on SSNHL-related admissions in China using a time-series approach. Long-term exposures to high DTR, RH values, low T-mean values, and all AP grades enhance the incidence of SSNHL in residents. Limiting exposure to extremes of ambient temperature and humidity may reduce the number of SSNHL-related hospital visits in the region. It is advisable to maintain a suitable living environment temperature and avoid extreme temperature fluctuations and high humidity. During periods of high air pollution, it is recommended to stay indoors and refrain from outdoor exercise.

Asp-tRNAAsn/Glu-tRNAGln amidotransferase A subunit-like amidase mediates the degradation of insecticide flonicamid by Variovorax boronicumulans CGMCC 4969 - Xue-Xiu Yu; Ke-Xin Chen; Pan-Pan Yuan; Yu-He Wang; Hua-Xiao Li; Yun-Xiu Zhao; Yi-jun Dai (Science of The Total Environment, 2024)

Axisymmetric finite strain consolidation model for soft soil consolidation with vertical drains under combined loading considering creep and non-Darcy flow - Peng-Lin Li; Zhen-Yu Yin; Ding-Bao Song; Jian-Hua Yin; Yu Pan (Geotextiles and Geomembranes, 2024)

Research on grouting reinforcement technology of fault crossing roadway in fully mechanized mining face with large dip angle - Weipeng Pan; Huaibin Li; Xinzhu Hua; Bin Liu; Chen Li (Bulletin of Engineering Geology and the Environment, 2024)

A theoretical investigation on the transformer oil pyrolysis mechanism and the effect of the small molecule acid in oils - Huijuan Wang; Wei Xia; Huimin Yu; Hua Chen; Yongli Pan; Yingxin Sun; Shengtao Li; Sheng Han (Fuel, 2024)

pH-shifted quinoa protein isolate-based nanocarriers for naringenin: Structure characterization and stability evaluation - Ying-Ying Chen; Qiang-Ming Li; Li-Hua Pan; Jian-Ping Luo; Xue-Ying Li; Xue-Qiang Zha (Food Hydrocolloids, 2024)

The polyphenols profile of co-fermented quinoa and black barley with Lactobacillus kisonensis and its in vitro bioactivities - Hui-Bin Jiang; Pan Nie; Zi-Han Lin; Chuang Zhu; Ling-Yue Zhong; Fen-Fen Wei; Yan Wu; Li-Hua Song (Food Bioscience, 2024)

Melatonin Enhanced Microglia M2 Polarization in Rat Model of Neuro-inflammation Via Regulating ER Stress/PPARδ/SIRT1 Signaling Axis - Hung-Chuan Pan; Cheng-Ning Yang; Wen-Jane Lee; Jason Sheehan; Sheng-Mao Wu; Hong-Shiu Chen; Mao-Hsun Lin; Li-Wei Shen; Shu-Hua Lee; Chin-Chang Shen; Liang-Yi Pan; Shing‑Hwa Liu; et al. (Journal of Neuroimmune Pharmacology, 2024)

Modulator of TMB-associated immune infiltration (MOTIF) predicts immunotherapy response and guides combination therapy - Zheng-Yu Qian; Yi-Qian Pan; Xue-Xin Li; Yan-Xing Chen; Hao-Xiang Wu; Ze-Xian Liu; Martin Kosar; Jiri Bartek; Zi-Xian Wang; Rui-Hua Xu (Science Bulletin, 2024)

Positively charged colloidal Nanoparticle/Polymer composites for High-Temperature capacitive energy Storage: A promising approach - Hua Wang; Zhichao Hu; Junhong Pan; Chaowei Zhong; Enzhu Li (Chemical Engineering Journal, 2024)

A Potential Source of Bias in Group-Level EEG Microstate Analysis - Michael Murphy; Jun Wang; Chenguang Jiang; Lei A. Wang; Nataliia Kozhemiako; Yining Wang; Jun Wang; Chenguang Jiang; Guanchen Gai; Kai Zou; Zhe Wang; Xiaoman Yu; et al. (Brain Topography, 2024)

Elucidating electron transfer pathways in N2OR catalysis for mitigation of N2O emissions: a comprehensive review - Lingxiu Liu; Minyu Suo; Changjie Shi; Nan Li; Hua Pan; Dzmitry Hrynsphan; Savitskaya Tatsiana; Raúl Robles-Iglesias; Zeyu Wang; Jun Chen (Reviews in Environmental Science and Bio/Technology, 2024)

Sugarcane Insect Pests in China: Species, Distribution and Population Dynamics - Xian-Kun Shang; Ji-Li Wei; Xue-Hong Pan; Cheng-Hua Huang; Amin Nikpay (Sugar Tech, 2024)

The two-way immunotoxicity in native fish induced by exudates of Microcystis aeruginosa: Immunostimulation and immunosuppression - Sen Zhao; Xuexiu Chang; Jun Li; Yanhua Zhu; Xiaofu Pan; Zexiang Hua; Jiaojiao Li (Journal of Hazardous Materials, 2024)

Preparation and characterization of lotus root starch based bioactive edible film containing quercetin-encapsulated nanoparticle and its effect on grape preservation - Ya-Fan Zeng; Ying-Ying Chen; Yuan-Yuan Deng; Chao Zheng; Cheng-Zhi Hong; Qiang-Ming Li; Xue-Fei Yang; Li-Hua Pan; Jian-Ping Luo; Xue-Ying Li; Xue-Qiang Zha (Carbohydrate Polymers, 2024)

Insights into the antibacterial activity and antibacterial mechanism of silver modified fullerene towards Staphylococcus aureus by multiple spectrometric examinations - Yin-Xu Pan; Qiu-Hui Xu; Hua-Ming Xiao; Chun-Ya Li (Chemosphere, 2023)

Over-expression of UDP-glycosyltransferase UGT353G2 confers resistance to neonicotinoids in whitefly (Bemisia tabaci) - Tian-hua Du; Cheng Yin; Lian-you Gui; Jin-jin Liang; Shao-nan Liu; Bu-li Fu; Chao He; Jing Yang; Xue-gao Wei; Pei-pan Gong; Ming-jiao Huang; Hu Xue; et al. (Pesticide Biochemistry and Physiology, 2023)

Laser boosting the influx of calcium ions to enhance gasdermin e-dependent pyroptosis driven by a dual-layer polydopamine nanoagonist - Xiaoling Qiu; Weixi Jiang; Xun Guo; Chier Du; Xiaoting Wang; Yu Tian; Hongjin An; Jingxue Wang; Yuanli Luo; Yuan Guo; Peng Luo; Hua Teng; et al. (Chemical Engineering Journal, 2023)

Functional-structural decoupling in visual network is associated with cognitive decline in patients with type 2 diabetes mellitus: evidence from a multimodal MRI analysis - Min-Hua Ni; Ying Yu; Yang Yang; Ze-Yang Li; Teng Ma; Hao Xie; Si-Ning Li; Pan Dai; Xin-Yu Cao; Yan-Yan Cui; Jun-Ling Zhu; Guang-Bin Cui; et al. (Brain Imaging and Behavior, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Neuroprotective effect of salidroside on hippocampal neurons in diabetic mice via PI3K/Akt/GSK-3β signaling pathway - Xue-Hua Wang; Zhong-Fu Zuo; Lu Meng; Qi Yang; Pan Lv; Li-Pan Zhao; Xiao-Bai Wang; Yu-Fei Wang; Ying Huang; Cong Fu; Wen-Qiang Liu; Xue-Zheng Liu; et al. (Psychopharmacology, 2023)

Rhein alleviates advanced glycation end products (AGEs)-induced inflammatory injury of diabetic cardiomyopathy in vitro and in vivo models - Shao-Yang Zhao; Huan-Huan Zhao; Bao-Hua Wang; Cui Shao; Wen-Jun Pan; Sai-Mei Li (Journal of Natural Medicines, 2023)

Baicalin promotes antiviral IFNs production and alleviates type I IFN-induced neutrophil inflammation - Li Li; Jia-Min Dong; He-He Ye; Man-Jing Jiang; Huan-Hua Yang; Lin-Pan Liang; Li-Jun Ning; Ying Wu (Journal of Natural Medicines, 2023)

Novel_miR-1517 mediates CYP6CM1 to regulate imidacloprid resistance in Bemisia tabaci (Hemiptera: Gennadius) - Pei-Pan Gong; Xue-Gao Wei; Shao-Nan Liu; Jing Yang; Bu-Li Fu; Jin-Jin Liang; Ming-Jiao Huang; Tian-Hua Du; Cheng Yin; Yao Ji; Chao He; Jin-Yu Hu; et al. (Pesticide Biochemistry and Physiology, 2023)

A complete assembly of the rice Nipponbare reference genome - Lianguang Shang; Wenchuang He; Tianyi Wang; Yingxue Yang; Qiang Xu; Xianjia Zhao; Longbo Yang; Hong Zhang; Xiaoxia Li; Yang Lv; Wu Chen; Shuo Cao; et al. (Molecular Plant, 2023)

Structural characteristics and thermal performances of lauric-myristic-palmitic acid introduced into modified water hyacinth porous biochar for thermal energy storage - Jiahong Zhou; Hua Fei; Qian He; Peisheng Li; Yucheng Pan; Ximei Liang (Science of The Total Environment, 2023)

Array electrochemiluminescence device with ultra-high sensitivity and selectivity for rapid visualized monitoring of trace radon in environment - Ziyu Wang; Yulin Li; Jian-Bin Pan; Meiyun Xu; Jing-Juan Xu; Daoben Hua (Journal of Hazardous Materials, 2023)

Heat transfer characteristics of premixed methane-air flame jet impinging on a hemispherical surface - Jinpeng Hua; Jianfeng Pan; Feiyang Li; Baowei Fan; Zhongjia Li; Abiodun Oluwaleke Ojo (Fuel, 2023)

QTL mapping and identification of candidate genes for cold tolerance at the germination stage in wild rice - Ying-Hua Pan; Bao-Xuan Nong; Lei Chen; Xing-Hai Yang; Xiu-Zhong Xia; Zong-Qiong Zhang; Dong-Jin Qing; Ju Gao; Cheng-Cui Huang; Dan-Ting Li; Guo-Fu Deng (Genes & Genomics, 2023)

Subcellular damages of pathogenic fungi combined with gene expression analysis reveals mechanisms that cold plasma controlling apricot disease - Yue Pan; Tingting Li; Caie Wu; Shuangfeng Guo; Gongjian Fan; Xiaojing Li; Dandan Zhou; Xiaowen Hua (Food Bioscience, 2023)

Screening of Artificial Diet Formulations for Sugarcane Stalk Borer Chilo sacchariphagus Bojer - Ji-li Wei; Xue-hong Pan; Xian-kun Shang; Cheng-hua Huang; Yong-lin Ma (Sugar Tech, 2023)

Olfactory Response and Preference of Telenomus dignus and Trichogramma chilonis to Chilo sacchariphagus - Xue-Hong Pan; Xian-Kun Shang; Cheng-Hua Huang; Ji-Li Wei (Sugar Tech, 2023)

Study on Flow Field Variation in Fracture Channel of Coalfield Fire - Qing-Wei Li; Hui-Pan Fan; Jia-Yu Feng; Li-Feng Ren; Teng Ma; Hao Zhang; Kun-Hua Liu; Yang Xiao (Natural Resources Research, 2023)

OrMKK3 Influences Morphology and Grain Size in Rice - Ying Hua Pan; Li Jun Gao; Yun Tao Liang; Yan Zhao; Hai Fu Liang; Wei Wei Chen; Xing Hai Yang; Dong Jin Qing; Ju Gao; Hao Wu; Juan Huang; Wei Yong Zhou; et al. (Journal of Plant Biology, 2023)

Two new compounds from edible mushroom Sarcomyxa edulis - Lan Yao; Jian-Hua Lv; Mei-Chen Pan; Lei Xing; Lu-Peng Wang; Chang-Tian Li; Shu-Yan Liu; Yu Li (Natural Product Research, 2023)

Effects of Nitrogen Fertilizer Rate Under Deep Placement on Grain Yield and Nitrogen Use Efficiency in Mechanical Pot-seedling Transplanting Rice - Yifei Wang; Yingqi Li; Yunhe Xie; Xiaoming Yang; Zhenzhen He; Hua Tian; Meiyang Duan; Xiangru Tang; Shenggang Pan (Journal of Plant Growth Regulation, 2023)

A microdots array-based fluoremetric assay with superwettability profile for simultaneous and separate analysis of iron and copper in red wine - Chenchen Xu; Qingqing Liu; Su Chu; Pan Li; Fengxiang Wang; Yanmei Si; Guojiang Mao; Choufei Wu; Hua Wang (Analytica Chimica Acta, 2023)

Immunotherapy in gastrointestinal cancers: advances, challenges, and countermeasures - Zi-Xian Wang; Yi-Qian Pan; Xuexin Li; Takeshi Tsubata; Rui-Hua Xu (Science Bulletin, 2023)

Shock waves, overpressure, and spontaneous ignition of pressurized hydrogen in T-shaped tubes - Yiming Jiang; Xuhai Pan; Tao Zhang; Zhilei Wang; Xilin Wang; Qingyuan Wang; Yunyu Li; Min Hua; Juncheng Jiang (Process Safety and Environmental Protection, 2023)

An Effective Microsatellite Marker Panel for Noninvasive Samples in Tibetan Macaques (Macaca thibetana) - Hua Liu; Jinxia Luo; Wei Hou; Xuan Pan; Yansen Cai; Jing Li (International Journal of Primatology, 2023)

Numerical investigation of drag reduction characteristics of flexible plate based on two way fluid-structure interaction - Yongcheng Li; Hua Zhang; Nan Zhang; Yinghua Li; Ziying Pan; Hailang Sun (Ocean Engineering, 2023)

A rapid selection strategy for umami peptide screening based on machine learning and molecular docking - Chen Li; Ying Hua; Daodong Pan; Lulu Qi; Chaogeng Xiao; Yongzhao Xiong; Wenjing Lu; Yali Dang; Xinchang Gao; Yufen Zhao (Food Chemistry, 2023)

Fine mapping and candidate gene analysis of qFL-A12-5: a fiber length-related QTL introgressed from Gossypium barbadense into Gossypium hirsutum - Xianghui Xiao; Ruixian Liu; Juwu Gong; Pengtao Li; Ziyin Li; Wankui Gong; Aiying Liu; Qun Ge; Xiaoying Deng; Shaoqi Li; Quanjia Chen; Hua Zhang; et al. (Theoretical and Applied Genetics, 2023)

Genome-wide association study reveals markers and candidate genes associated with growth in the rice flower carp, an economic fish species of integrated rice-fish culture in China - Hui Luo; Xianhui Pan; Yin Huang; Zhe Li; Hua Ye; Kangqi Zhou; Luting Wen; Junqi Qin; Wenping He; Xuesong Du; Dapeng Wang; Yong Lin (Frontiers in Marine Science, 2023)
The rice flower carp ( Cyprinus carpio ) is an important fish in integrated rice-fishery farming. Here, we performed the first genome-wide association study (GWAS) for seven growth traits (including body mass, total length, body length, body height, body width, caudal-peduncle depth, and eye spacing) in 200 rice flower carp samples using 369,688 high-quality SNPs and 42,225 indels obtained by double-digest genotyping-by-sequencing (ddGBS). The morphometrics of these traits were highly correlated (Pearson’s correlation coefficients = 0.74–0.99, p < 0.001). GWAS detected 15, 5, 4, 26, 7, 16, and 17 loci significant associated (-log10P ≥ 5) with body mass, total length, body length, body width, body height, caudal-peduncle depth, and eye spacing, respectively. Subsequently, within the 50 kb upstream and downstream regions surrounding these significant loci, 38, 19, 18, 20, 52, 27, and 37 candidate genes for the seven growth traits were detected, respectively. Importantly, B6_4352672 and A8_4978825 were significantly associated with more than five growth traits. These results showed loci significantly associated with more than five growth traits will be helpful for future marker-assisted selection (MAS). Interestingly, chromosomes A8 and B25 had many loci significantly associated with growth traits, most of which were shared among multiple growth-related traits. These results indicated that chromosome A8 and B25 may be closely related to growth traits. Our findings not only help understand the genetic architecture of growth traits in fish but facilitate the identification of candidate genes for marker-assisted selection towards breeding faster-growing rice flower carp in the future.

Comprehensive performance evaluation of plasma vitrification for detoxification and valorization of residual wastes - Yao-Jian Li; Si-Lu Pei; Zhong-Hua Sun; Lei Zhong; Cheng-Chun He; Shu-Yuan Pan (Critical Reviews in Environmental Science and Technology, 2023)

Two new terpenoids and other constituents from Salvia cavaleriei and their antibacterial activities - Yu-Min Zhao; Ke Li; Han-Fei Liu; Jin-Yu Li; Jian Fu; Hua-Yong Lou; Wei-Dong Pan (Phytochemistry Letters, 2023)

Corrigendum to “Dendrobium huoshanense stem polysaccharide ameliorates rheumatoid arthritis in mice via inhibition of inflammatory signaling pathways” [Carbohydr. Polym. 258 (2021) 117657] - Zhen-Zi Shang; Dan-Yang Qin; Qiang-Ming Li; Xue-Qiang Zha; Li-Hua Pan; Dai-Yin Peng; Jian-Ping Luo (Carbohydrate Polymers, 2023)

Effects of urban particulate matter on gut microbiome and partial schizophrenia-like symptoms in mice: Evidence from shotgun metagenomic and metabolomic profiling - Weizhuo Yi; Yifu Ji; Hua Gao; Shengyong Luo; Rubing Pan; Jian Song; Yangyang He; Yuxuan Li; Yudong Wu; Shuangshuang Yan; Yunfeng Liang; Xiaoni Sun; et al. (Science of The Total Environment, 2023)

Diterpenoids with anti-inflammatory activity from Euphorbia wallichii - Yali Wang; Dejuan Sun; Qinghua Jiang; Liangliang Xiong; Na Zhang; Yingni Pan; Hua Li; Lixia Chen (Phytochemistry, 2023)

Effect of flow directions in the T-shaped tubes on the shock wave and spontaneous ignition of pressurized hydrogen - Yiming Jiang; Xuhai Pan; Min Hua; Zhilei Wang; Tao Zhang; Qingyuan Wang; Yunyu Li; Andong Yu; Juncheng Jiang (Fuel, 2023)

Discrimination of the harvesting season of green tea by alcohol/salt-based aqueous two-phase systems combined with chemometric analysis - Xiao-Hua Zhang; Hui-Na Cui; Jing-Jing Zheng; Xiang-Dong Qing; Kai-Long Yang; Ya-Qian Zhang; Lu-Meng Ren; Le-Yuan Pan; Xiao-Li Yin (Food Research International, 2023)

Concurrent classic driver oncogenes mutation with ROS1 rearrangement predicts superior clinical outcome in NSCLC patients - Dandan Li; Hua Jiang; Faguang Jin; Lei Pan; Yonghong Xie; Liang Zhang; Chunmei Li (Genes & Genomics, 2023)

Lipocalin-2-Mediated Insufficient Oligodendrocyte Progenitor Cell Remyelination for White Matter Injury After Subarachnoid Hemorrhage via SCL22A17 Receptor/Early Growth Response Protein 1 Signaling - Qiang Li; Xufang Ru; Yang Yang; Hengli Zhao; Jie Qu; Weixiang Chen; Pengyu Pan; Huaizhen Ruan; Chaojun Li; Yujie Chen; Hua Feng (Neuroscience Bulletin, 2022)
Insufficient remyelination due to impaired oligodendrocyte precursor cell (OPC) differentiation and maturation is strongly associated with irreversible white matter injury (WMI) and neurological deficits. We analyzed whole transcriptome expression to elucidate the potential role and underlying mechanism of action of lipocalin-2 (LCN2) in OPC differentiation and WMI and identified the receptor SCL22A17 and downstream transcription factor early growth response protein 1 (EGR1) as the key signals contributing to LCN2-mediated insufficient OPC remyelination. In LCN-knockdown and OPC EGR1 conditional-knockout mice, we discovered enhanced OPC differentiation in developing and injured white matter (WM); consistent with this, the specific inactivation of LCN2/SCl22A17/EGR1 signaling promoted remyelination and neurological recovery in both atypical, acute WMI due to subarachnoid hemorrhage and typical, chronic WMI due to multiple sclerosis. This potentially represents a novel strategy to enhance differentiation and remyelination in patients with white matter injury.

An association study on the risk, glucocorticoids effectiveness, and prognosis of systemic lupus erythematosus: insight from mitochondrial DNA copy number - Zhen Li; Qi-Qun Zong; Chun-Xia Zhai; Guang-Hui Yu; Wan-Qin Hu; Yu-Hua Wang; Lin-Lin Wang; Zi-Ye Yan; Ting-Yu Zhang; Ying Teng; Shuang Liu; Jing Cai; et al. (Immunologic Research, 2022)

The occurrence and partition of total petroleum hydrocarbons in sediment, seawater, and biota of the eastern sea area of Shandong Peninsula, China - Xue Wang; Chunhui Wang; Weiwei Jiang; Yulong Pan; Fujuan Li; Hua Tian (Environmental Science and Pollution Research, 2022)

Investigating Population Dynamics and Sex Structure of Exolontha castanea Chang (Coleoptera: Melolonthidae) Using Light Traps in Sugarcane Fields in China - Xian-kun Shang; Ji-li Wei; Wei Liu; Xue-hong Pan; Cheng-hua Huang; Amin Nikpay; François-Régis Goebel (Sugar Tech, 2022)

Correction to: Three novel Fusarium mutualists of ambrosia beetle Euwallacea interjectus in China - Shengchang Lai; Chen Zhao; You Li; Yang Zhou; Lei Zhong; Cailou Qiu; Hua Wang; Yuwen Pan; Lulu Dai; Dejun Hao (Mycological Progress, 2022)

Three novel Fusarium mutualists of ambrosia beetle Euwallacea interjectus in China - Shengchang Lai; Chen Zhao; You Li; Yang Zhou; Lei Zhong; Cailou Qiu; Hua Wang; Yuwen Pan; Lulu Dai; Dejun Hao (Mycological Progress, 2022)

Comparative Analysis of Endogenous Hormones and Metabolite Profiles in Early-Spring Flowering Plants and Unflowered Plants Revealing the Strategy of Blossom - Xue Yan; Jia Liu; Ke-Xin Wu; Nan Yang; Li-Ben Pan; Ying Song; Yang Liu; Zhong-Hua Tang (Journal of Plant Growth Regulation, 2022)

Why empresses have more sons? Maternal instant social condition determines it - Yan-Peng Li; Wei Ding; Zhi-Pang Huang; Ru-Liang Pan; Na Li; Guo-Peng Ren; Liang-Wei Cui; Qing-hua Cai; Wen Xiao (Behavioral Ecology and Sociobiology, 2022)
Sexual selection echoed by the sex ratio is a critical issue in evolution and reproductive biology studies, and the second sex ratio (sex ratio at birth, SRB) is an important evaluation indicator for sex regulation. However, broad debates on sex ratio at birth exist due to the lack of a clear spatiotemporal genealogical database. This study explicitly tests the Trivers and Willard’s hypothesis stating that parents with good social conditions tend to show a male-biased SRB. Using a database of Chinese imperial families from 211BC to 1912 (2142 years) which avoids the spatiotemporal confusion of data thanks to its clear boundaries and long timespan, we found that a proportion of males at birth was 0.54. In particular, the results indicate that the empresses generated a significantly higher male-biased SRB than the concubines within the imperial harems (0.61 vs 0.53), while the SRB of concubines was not higher than ordinary people (0.53 vs 0.52). A significant difference of SRB before and after empress coronation (0.48 vs 0.65) was detected, indicating that the change to a higher social status is the leading cause of a biased SRB. These findings suggest that mothers with privileged instant social conditions tend to generate more boys than girls. In other words, a higher maternal social rank during the conception period, instead of rich resources, forms the primary mechanism regulating the SRB. Significance statement Adaptive sex ratio has been a debatable topic difficult to clearly verify since the publication of Trivers and Willard Hypothesis in 1973, which proposes that parents who have good conditions should produce more male offspring. The one reason is that the validity and sample size of the databases used contained unavoidable confounding noise, both genealogically and genetically. To overcome these issues, we specifically compiled a historical database of Chinese imperial families, which are characterized by a confined mating harem and unique eunuch system, guaranteeing biological and genetic purity with precise genealogical relationships and genetic linkages between the parents and the offspring. Thus, this is an extraordinary effort to clarify the hypotheses proposed by TWH and other hypotheses.

Bone Marrow-Derived Alk1 Mutant Endothelial Cells and Clonally Expanded Somatic Alk1 Mutant Endothelial Cells Contribute to the Development of Brain Arteriovenous Malformations in Mice - Sonali S. Shaligram; Rui Zhang; Wan Zhu; Li Ma; Man Luo; Qiang Li; Miriam Weiss; Thomas Arnold; Nicolas Santander; Rich Liang; Leandro do Prado; Chaoliang Tang; et al. (Translational Stroke Research, 2022)

LncDACH1 promotes mitochondrial oxidative stress of cardiomyocytes by interacting with sirtuin3 and aggravates diabetic cardiomyopathy - Qi Zhang; Danyang Li; Xue Dong; Xiaowen Zhang; Junwu Liu; Lili Peng; Bo Meng; Qi Hua; Xinyu Pei; Lu Zhao; Xiaoxi Hu; Yang Zhang; et al. (Science China Life Sciences, 2022)

Sevoflurane inhibits the malignant phenotypes of glioma through regulating miR-146b-5p/NFIB axis - Haili Wang; Guofang Cheng; Lili Quan; Haibo Qu; Ailing Yang; Jiangge Ye; Yuanbo Feng; Xiaofang Li; Xiaoli Shi; Hua Pan (Metabolic Brain Disease, 2022)

Additional Nitrogen Application Under Different Water Regimes at Tillering Stage Enhanced Rice Yield and 2-Acetyl-1-Pyrroline (2AP) Content in Fragrant Rice - Yanhong Li; Zhaowen Mo; Yuzhan Li; Jun Nie; Leilei Kong; Umair Ashraf; Shenggang Pan; Meiyang Duan; Hua Tian; Xiangru Tang (Journal of Plant Growth Regulation, 2022)

Identification of PDXDC1 as a novel pleiotropic susceptibility locus shared between lumbar spine bone mineral density and birth weight - Yu-Qian Song; Shi-Di Hu; Xu Lin; Xiang-He Meng; Xiao Wang; Yin-Hua Zhang; Cheng Peng; Rui Gong; Tao Xu; Tong Zhang; Chen-Zhong Li; Dao-Yan Pan; et al. (Journal of Molecular Medicine, 2022)
An increasing number of epidemiological studies have suggested that birth weight (BW) may be a determinant of bone health later in life, although the underlying genetic mechanism remains unclear. Here, we applied a pleiotropic conditional false discovery rate (cFDR) approach to the genome-wide association study (GWAS) summary statistics for lumbar spine bone mineral density (LS BMD) and BW, aiming to identify novel susceptibility variants shared between these two traits. We detected 5 novel potential pleiotropic loci which are located at or near 7 different genes ( NTAN1 , PDXDC1 , CACNA1G , JAG1 , FAT1P1 , CCDC170 , ESR1 ), among which PDXDC1 and FAT1P1 have not previously been linked to these phenotypes. To partially validate the findings, we demonstrated that the expression of PDXDC1 was dramatically reduced in ovariectomized (OVX) mice in comparison with sham-operated (SHAM) mice in both the growth plate and trabecula bone. Furthermore, immunohistochemistry assay with serial sections showed that both osteoclasts and osteoblasts express PDXDC1 , supporting its potential role in bone metabolism. In conclusion, our study provides insights into some shared genetic mechanisms for BMD and BW as well as a novel potential therapeutic target for the prevention of OP in the early stages of the disease development. Key messages We investigated pleiotropy-informed enrichment between LS BMD and BW. We identified genetic variants related to both LS BMD and BW by utilizing a cFDR approach. PDXDC1 is a novel pleiotropic gene which may be related to both LS BMD and BW. Elevated expression of PDXDC1 is related to higher BMD and lower ratio n-6/n-3 PUFA indicating a bone protective effect of PDXDC1.

Effects of thermal treatment on the macroscopic physical properties and microstructure of Beishan fine-grained granite - Zu-Xi Liu; Yun Wu; Xiao-Zhao Li; Zhen Huang; Jian Lin; Xiao-Hua Pan (Bulletin of Engineering Geology and the Environment, 2022)

Coupling effect of biocementation-fiber reinforcement on mechanical behavior of calcareous sand for ocean engineering - Chao-Sheng Tang; Hao Li; Xiao-Hua Pan; Li-Yang Yin; Liang Cheng; Qing Cheng; Bo Liu; Bin Shi (Bulletin of Engineering Geology and the Environment, 2022)

Three new dimeric 2-(2-phenylethyl)chromones from artificial agarwood of Aquilaria sinensis - Pan Xiang; Wen-Hua Dong; Cai-Hong Cai; Wei Li; Li-Man Zhou; Hao-Fu Dai; Hui-Qin Chen; Wen-Li Mei (Natural Product Research, 2021)

Experimental and comparative study of Chinese commercial improved coal-fired cooking and space-heating stoves - Riaz Ahmad; Adnan Abbas; Wang Jufei; Li Hua; Muhammad Sultan; Bohong Li; Samuel M Nyambura; Pan Xingjia (Environmental Science and Pollution Research, 2021)

Simulation and test of the movement process of mixed flow composed of slurry and coarse particle - Xian-jun Ji; Ying Liang; Guo-qiang Ou; Hua-li Pan (European Journal of Environmental and Civil Engineering, 2021)

Diversity, metabolism and cultivation of archaea in mangrove ecosystems - Cui-Jing Zhang; Yu-Lian Chen; Yi-Hua Sun; Jie Pan; Ming-Wei Cai; Meng Li (Marine Life Science & Technology, 2021)

Change detection in SAR images based on superpixel segmentation and image regression - Rui Zhao; Guo-Hua Peng; Wei-dong Yan; Lu-Lu Pan; Li-Ya Wang (Earth Science Informatics, 2021)

Deep Placement of Nitrogen Fertilizer Affects Grain Yield, Nitrogen Recovery Efficiency, and Root Characteristics in Direct-Seeded Rice in South China - Yunyan Chen; Pingshan Fan; Zhaowen Mo; Leilei Kong; Hua Tian; Meiyang Duan; Lin Li; Liji Wu; Zaimang Wang; Xiangru Tang; Shenggang Pan (Journal of Plant Growth Regulation, 2021)

Modes of genetic adaptations underlying functional innovations in the rumen - Xiangyu Pan; Yudong Cai; Zongjun Li; Xianqing Chen; Rasmus Heller; Nini Wang; Yu Wang; Chen Zhao; Yong Wang; Han Xu; Songhai Li; Ming Li; et al. (Science China Life Sciences, 2021)

Straw Incorporation Coupled with Deep Placement of Nitrogen Fertilizer Improved Grain Yield and Nitrogen Use Efficiency in Direct-Seeded Rice - Yunyan Chen; Pingshan Fan; Lin Li; Hua Tian; Umair Ashraf; Zhaowen Mo; Meiyang Duan; Qiantong Wu; Zheng Zhang; Xiangru Tang; Shenggang Pan (Journal of Soil Science and Plant Nutrition, 2020)

Evaluation of the Parasitism Capacity of Egg Parasitoid Telenomus dignus on Chilo sacchariphagus - Xue-Hong Pan; Ji-Li Wei; Xian-Kun Shang; Cheng-Hua Huang; Amin Nikpay; François-Régis Goebel (Sugar Tech, 2020)

Structural features of an acidic polysaccharide with the potential of promoting osteoblast differentiation from Lycium ruthenicum Murr. - Shu-Qi Wang; Bing Liu; Su Liu; Song-Zi Xie; Li-Hua Pan; Xue-Qiang Zha; Qiang-Ming Li; Jian-Ping Luo (Natural Product Research, 2020)

γ-Aminobutyric Acid Regulates Grain Yield Formation in Different Fragrant Rice Genotypes Under Different Nitrogen Levels - Yuzhan Li; Rifang Lai; Wu Li; Jiaqi Liu; Mingzhi Huang; Yijing Tang; Xiangru Tang; Shenggang Pan; Meiyang Duan; Hua Tian; Longmei Wu; Shuli Wang; et al. (Journal of Plant Growth Regulation, 2020)

Anti-inflammatory bibenzyls from the stems of Dendrobium huoshanense via bioassay guided isolation - Qiang-Ming Li; Hui Jiang; Xue-Qiang Zha; De-Ling Wu; Li-Hua Pan; Jun Duan; Jian Liu; Jian-Ping Luo (Natural Product Research, 2020)

Regulation of growth performance and lipid metabolism in juvenile grass carp (Ctenopharyngodon idella) with honeysuckle (Lonicera japonica) extract - Xiao-Lin Meng; Zhen-Xiang Zhu; Rong-Hua Lu; Shuai Li; Wen-Pan Hu; Chao-Bin Qin; Xiao Yan; Guo-kun Yang; Guo-Xing Nie (Fish Physiology and Biochemistry, 2019)

Potassium Stimulation of IAA Transport Mediated by the Arabidopsis Importer AUX1 Investigated in a Heterologous Yeast System - Li-Kun Huang; Ya-Yun Liao; Wei-Hua Lin; Shih-Ming Lin; Tzu-Yin Liu; Ching-Hung Lee; Rong-Long Pan (The Journal of Membrane Biology, 2019)

Antifungal Susceptibility Profile of Candida Albicans Isolated from Vulvovaginal Candidiasis in Xinjiang Province of China - Liang Yan; Xiao-dong Wang; Seyedmojtaba Seyedmousavi; Juan-na Yuan; Palida Abulize; Wei-hua Pan; Nong Yu; Ya-li Yang; Hai-qing Hu; Wan-qing Liao; Shu-wen Deng (Mycopathologia, 2019)

Field-evolved resistance and cross-resistance of the two-spotted spider mite, Tetranychus urticae, to bifenazate, cyenopyrafen and SYP-9625 - Jin-Cui Chen; Ya-Jun Gong; Pan Shi; Ze-Hua Wang; Li-Jun Cao; Peng Wang; Shu-Jun Wei (Experimental and Applied Acarology, 2019)

Mechanism of toppling and deformation in hard rock slope: a case of bank slope of Hydropower Station, Qinghai Province, China - Jun-chao Cai; Neng-pan Ju; Run-qiu Huang; Da Zheng; Wei-hua Zhao; Long-qi Li; Jian Huang (Journal of Mountain Science, 2019)

Organic carbon quality, composition of main microbial groups, enzyme activities, and temperature sensitivity of soil respiration of an acid paddy soil treated with biochar - Junhui Chen; De Chen; Qiufang Xu; Jeffry J. Fuhrmann; Lianqing Li; Genxing Pan; Yongfu Li; Hua Qin; Chenfei Liang; Xuan Sun (Biology and Fertility of Soils, 2019)

Role of prefrontal cortex in the extinction of drug memories - Wen-Hua Zhang; Ke-Xin Cao; Zeng-Bo Ding; Jian-Li Yang; Bing-Xing Pan; Yan-Xue Xue (Psychopharmacology, 2019)

The IMPDH inhibitors, ribavirin and mycophenolic acid, inhibit peste des petits ruminants virus infection - Qiu-yan Chang; Fu-cheng Guo; Xue-rui Li; Jian-hua Zhou; Xuepeng Cai; Qiuwei Pan; Xiao-xia Ma (Veterinary Research Communications, 2018)

Positive PCNA and Ki-67 Expression in the Testis Correlates with Spermatogenesis Dysfunction in Fluoride-Treated Rats - Wen-peng Zhao; Hong-wei Wang; Jing Liu; Pan-pan Tan; Xiang-long Luo; Shi-quan Zhu; Xue-li Chen; Bian-hua Zhou (Biological Trace Element Research, 2018)

Effect of Source-Classified Collection of Municipal Solid Waste on Heavy Metals and Pozzolanic Properties of Incineration Residues - Dezhi Shi; Pan Wang; Xiaoyi Xu; Li Gu; Lei Li; Hua Ma; Chunyan Hu (International Journal of Environmental Research, 2018)

Long runout mechanism of the Shenzhen 2015 landslide: insights from a two-phase flow viewpoint - Cheng Qiao; Guo-qiang Ou; Hua-li Pan; Chao-jun Ouyang; Yang Jia (Journal of Mountain Science, 2018)

Associations of HSP90AA2 gene polymorphisms with disease susceptibility, glucocorticoids efficacy and health-related quality of life in Chinese systemic lupus erythematosus patients - Man Zhang; Su-Su Li; Qiao-Mei Xie; Jian-Hua Xu; Xiu-Xiu Sun; Fa-Ming Pan; Sheng-Qian Xu; Sheng-Xiu Liu; Jin-Hui Tao; Shuang Liu; Jing Cai; Pei-Ling Chen; et al. (Genes & Genomics, 2018)

The role of HMGB1 in BMSC transplantation for treating MODS in rats - Guanghui Xiu; Jie Sun; Xiuling Li; Hua Jin; Yichao Zhu; Xia Zhou; Ping Liu; Xinghua Pan; Jian Li; Bin Ling (Cell and Tissue Research, 2018)

De novo assembly of mitochondrial genomes provides insights into genetic diversity and molecular evolution in wild boars and domestic pigs - Pan Ni; Ali Akbar Bhuiyan; Jian-Hai Chen; Jingjin Li; Cheng Zhang; Shuhong Zhao; Xiaoyong Du; Hua Li; Hui Yu; Xiangdong Liu; Kui Li (Genetica, 2018)

Regulation of H+-pyrophosphatase by 14-3-3 Proteins from Arabidopsis thaliana - Yu-Di Hsu; Yu-Fen Huang; Yih-Jiuan Pan; Li-Kun Huang; Ya-Yun Liao; Wei-Hua Lin; Tzu-Yin Liu; Ching-Hung Lee; Rong-Long Pan (The Journal of Membrane Biology, 2018)

The effects of rainfall regimes and terracing on runoff and erosion in the Three Gorges area, China - Qin-xue Xu; Pan Wu; Jun-feng Dai; Tian-wei Wang; Zhao-xia Li; Chong-fa Cai; Zhi-hua Shi (Environmental Science and Pollution Research, 2018)

CAsubtype: An R Package to Identify Gene Sets Predictive of Cancer Subtypes and Clinical Outcomes - Hualei Kong; Pan Tong; Xiaodong Zhao; Jielin Sun; Hua Li (Interdisciplinary Sciences: Computational Life Sciences, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

Short hairpin RNA interference targeting interleukin 1 receptor type I in the paraventricular nucleus attenuates hypertension in rats - Peng Lu; Shu-jun Jiang; Hong Pan; Ai-li Xu; Gui-hua Wang; Chun-lei Ma; Zhen Shi (Pflügers Archiv - European Journal of Physiology, 2018)

AMPK/NF-κB signaling pathway regulated by ghrelin participates in the regulation of HUVEC and THP1 Inflammation - Min Zhang; Shuping Wang; Zhicheng Pan; Tiantong Ou; Jianwei Ma; Hua Liu; Ruogu Li; Ping Yang; Wenzheng Han; Shaofeng Guan; Xumin Hou; Weiyi Fang; et al. (Molecular and Cellular Biochemistry, 2018)

Phospholipid and fatty acid composition in leaves and roots of ten autumn chrysanthemum cultivars grown at low temperature - Yan Li; Yonghua Li; Pan Yang; Hua’ao Zhang; Dan He (Horticulture, Environment, and Biotechnology, 2017)

Dissipation and Residue of Acephate and Its Metabolite Metamidophos in Peach and Pear Under Field Conditions - Xiangwei Wu; Jiaying Xue; Dandan Pan; Laijia Jin; Taozhong Shi; Xiaoxin Cheng; Qing X. Li; Rimao Hua (International Journal of Environmental Research, 2017)

Three new resin glycosides compounds from Argyreia acuta and their α -glucosidase inhibitory activity - Li Wang; You-Shao Yan; Hong-Hua Cui; Yong-Qin Yin; Jie-Tao Pan; Bang-Wei Yu (Natural Product Research, 2017)

Association of oral endothelin receptor antagonists with risks of cardiovascular events and mortality: meta-analysis of randomized controlled trials - Yu Pan; Chun Hu; Pei Hua Chen; Yan Hong Gu; Qing Yan Qiao; Li Hua Pan; Dong Chi Zhou; Hui Fang Gu; Shun Kun Fu; Hui Min Jin (European Journal of Clinical Pharmacology, 2017)

Netrin-1 Contributes to Myelinated Afferent Fiber Sprouting and Neuropathic Pain - Cai-Hua Wu; Xiao-Cui Yuan; Fang Gao; Hong-Ping Li; Jie Cao; Yan-Shen Liu; Wei Yu; Bo Tian; Xian-Fang Meng; Jing Shi; Hui-Lin Pan; Man Li (Molecular Neurobiology, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

The Hilbert–Huang Transform-Based Denoising Method for the TEM Response of a PRBS Source Signal - Li Hai; Xue Guo-qiang; Zhao Pan; Zhong Hua-sen; Muhammad Younis Khan (Pure and Applied Geophysics, 2016)

Signaling Mechanism of Cannabinoid Receptor-2 Activation-Induced β-Endorphin Release - Fang Gao; Ling-Hong Zhang; Tang-Feng Su; Lin Li; Rui Zhou; Miao Peng; Cai-Hua Wu; Xiao-Cui Yuan; Ning Sun; Xian-Fang Meng; Bo Tian; Jing Shi; et al. (Molecular Neurobiology, 2016)

The impacts of migrant workers consumption on energy use and CO2 emissions in China - Jing-Li Fan; Hua Liao; Bao-Jun Tang; Su-Yan Pan; Hao Yu; Yi-Ming Wei (Natural Hazards, 2016)

Risk assessment of maize drought disaster in southwest China using the Environmental Policy Integrated Climate model - Hui-cong Jia; Dong-hua Pan; Jing Li; Wan-chang Zhang; Rasul Ghulam (Journal of Mountain Science, 2016)

Undrained Dynamic Strength Behavior of Saturated Nanjing Fine Sand under Wave Load - Guoxing Chen; Hua Pan; Xiaojun Li (Marine Georesources & Geotechnology, 2016)

Silencing of dehydrin CaDHN1 diminishes tolerance to multiple abiotic stresses in Capsicum annuum L. - Ru-gang Chen; Hua Jing; Wei-li Guo; Shu-Bin Wang; Fang Ma; Bao-Gui Pan; Zhen-Hui Gong (Plant Cell Reports, 2015)

The roles of methanogens and acetogens in dechlorination of trichloroethene using different electron donors - Li-Lian Wen; Yin Zhang; Ya-Wei Pan; Wen-Qi Wu; Shao-Hua Meng; Chen Zhou; Youneng Tang; Ping Zheng; He-Ping Zhao (Environmental Science and Pollution Research, 2015)

High-speed ring shear tests to study the motion and acceleration processes of the Yingong landslide - Ming-jian Hu; Hua-li Pan; Chang-qi Zhu; Fa-wu Wang (Journal of Mountain Science, 2015)

The SARP Family Regulator Txn9 and Two-Component Response Regulator Txn11 are Key Activators for Trioxacarcin Biosynthesis in Streptomyces bottropensis - Kui Yang; Li-Hua Qi; Mei Zhang; Xian-Feng Hou; Hai-Xue Pan; Gong-Li Tang; Wei Wang; Hua Yuan (Current Microbiology, 2015)

Debris flow formation process and critical hydrodynamic conditions in the meizoseismal area of the Wenchuan earthquake - Jun Wang; Yan Yu; Hua-li Pan; Cheng Qiao; Guo-qiang Ou (Journal of Mountain Science, 2015)

A novel species of ellipsoidal multicellular magnetotactic prokaryotes from L ake Y uehu in C hina - Yi‐Ran Chen; Rui Zhang; Hai‐Jian Du; Hong‐Miao Pan; Wen‐Yan Zhang; Ke Zhou; Jin‐Hua Li; Tian Xiao; Long‐Fei Wu (Environmental Microbiology, 2015)
Summary Two morphotypes of multicellular magnetotactic prokaryotes ( MMPs ) have been identified: spherical (several species) and ellipsoidal (previously one species). Here, we report novel ellipsoidal MMPs that are ∼ 10 × 8 μm in size, and composed of about 86 cells arranged in six to eight interlaced circles. Each MMP was composed of cells that synthesized either bullet‐shaped magnetite magnetosomes alone, or both bullet‐shaped magnetite and rectangular greigite magnetosomes. They showed north‐seeking magnetotaxis, ping‐pong motility and negative phototaxis at a velocity up to 300 μm s −1 . During reproduction, they divided along either their long‐ or short‐body axes. For genetic analysis, we sorted the ellipsoidal MMPs with micromanipulation and amplified their genomes using multiple displacement amplification. We sequenced the 16 S r RNA gene and found 6.9% sequence divergence from that of ellipsoidal MMPs , Candidatus Magnetananas tsingtaoensis and > 8.3% divergence from those of spherical MMPs . Therefore, the novel MMPs belong to different species and genus compared with the currently known ellipsoidal and spherical MMPs respectively. The novel MMPs display a morphological cell differentiation, implying a potential division of labour. These findings provide new insights into the diversity of MMPs in general, and contribute to our understanding of the evolution of multicellularity among prokaryotes.

Mechanism of downcutting erosion of debris flow over a movable bed - Hua-li Pan; Jiang-cheng Huang; Guo-qiang Ou (Journal of Mountain Science, 2015)

Research progress in China on the tropical atmospheric intraseasonal oscillation - Chongyin Li; Jian Ling; Jie Song; Jing Pan; Hua Tian; Xiong Chen (Journal of Meteorological Research, 2014)

Analysis of synonymous codon usage in enterovirus 71 - Hua Zhang; Hong-wei Cao; Feng-qi Li; Zi-ye Pan; Zhi-jun Wu; Yan-hong Wang; Yu-dong Cui (VirusDisease, 2014)

Is right ventricular mid-septal pacing superior to apical pacing in patients with high degree atrio-ventricular block and moderately depressed left ventricular function? - Kang Chen; Ye Mao; Shao-hua Liu; Qiong Wu; Qing-zhi Luo; Wen-qi Pan; Qi Jin; Ning Zhang; Tian-you Ling; Ying Chen; Gang Gu; Wei-feng Shen; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Identification of BACH2 as a susceptibility gene for Graves’ disease in the Chinese Han population based on a three-stage genome-wide association study - Wei Liu; Hai-Ning Wang; Zhao-Hui Gu; Shao-Ying Yang; Xiao-Ping Ye; Chun-Ming Pan; Shuang-Xia Zhao; Li-Qiong Xue; Hui-Jun Xie; Sha-Sha Yu; Cui-Cui Guo; Wen-Hua Du; et al. (Human Genetics, 2014)

Reston virus in domestic pigs in China - Yangyang Pan; Wen Zhang; Li Cui; Xiuguo Hua; Meng Wang; Qiaoying Zeng (Archives of Virology, 2014)

Nonvirus encoded proteins could be embedded into Bombyx mori cypovirus polyhedra - Yi-ling Zhang; Ren-yu Xue; Guang-li Cao; Xiang-kun Meng; Yue-xiong Zhu; Zhong-hua Pan; Cheng-liang Gong (Molecular Biology Reports, 2014)

Statistical analysis of sudden chemical leakage accidents reported in China between 2006 and 2011 - Yang Li; Hua Ping; Zhi-Hong Ma; Li-Gang Pan (Environmental Science and Pollution Research, 2014)

Early Carboniferous intra-oceanic arc and back-arc basin system in the West Junggar, NW China - Ping Shen; Hongdi Pan; Wenjiao Xiao; Xian-hua Li; Huawu Dai; Heping Zhu (International Geology Review, 2013)

Local scour and the laws of scour pit’s shape downstream of debris flow sabo dam - Hua-li Pan; Shun Yang; Guo-qiang Ou; Jiang-cheng Huang (Journal of Mountain Science, 2013)

Landslides & debris flows formation from gravelly soil surface erosion and particle losses in Jiangjia Ravine - Ming-jian Hu; Hua-li Pan; Hou-zhen Wei; Ren Wang; Ying A (Journal of Mountain Science, 2013)

Isolation and characterization of fifteen microsatellite loci in the Tibetan fox (Vulpes ferrilata) - MIN LI; XIAO MING WANG; WEI BIN JIANG; PAN YU HUA; ZHENG HUAN WANG (Journal of Genetics, 2013)

Association between CYP1A1 polymorphisms and esophageal cancer: a meta-analysis - Fang-Fang Shen; Fu-You Zhou; Qi-Si Xue; Ying Pan; Lu Zheng; Hua Zhang; Li-Dong Wang; Hou-Feng Zheng (Molecular Biology Reports, 2013)

Genetic diversity and evolutionary characterization of Chinese porcine reproductive and respiratory syndrome viruses based on NSP2 and ORF5 - Jian-Kui Liu; Chun-Hua Wei; Xiao-Yan Yang; Xi-Lin Hou; AI-Ling Dai; Xiao-Hua Li; Mei-Kang Wei; Xiu-Zhen Pan (Archives of Virology, 2013)

Environmental connections of novel avian-origin H7N9 influenza virus infection and virus adaptation to the human - Jun Li; XinFen Yu; XiaoYing Pu; Li Xie; YongXiang Sun; HaiXia Xiao; FenJuan Wang; Hua Din; Ying Wu; Di Liu; GuoQiu Zhao; Jun Liu; et al. (Science China Life Sciences, 2013)

Adaptation of spherical multicellular magnetotactic prokaryotes to the geochemically variable habitat of an intertidal zone - Ke Zhou; Wen‐Yan Zhang; Hong‐Miao Pan; Jin‐Hua Li; Hai‐Dong Yue; Tian Xiao; Long‐Fei Wu (Environmental Microbiology, 2013)
Summary A combination of microscopic, molecular and biogeochemical methods was used to study the structure, phylogenetics and vertical distribution of spherical multicellular magnetotactic prokaryotes ( MMPs ) of intertidal sediments in the Y ellow S ea. These MMPs were 5.5 μm in diameter and composed of approximately 15–30 cells. They synthesized bullet‐shaped magnetites in chains or clusters. Phylogenetic analysis of 16 S rRNA gene sequences suggested that these MMPs represent a novel species affiliated to the D eltaproteobacteria. To study their vertical distribution and the relationship to geochemical parameters, sediment cores were collected after the redox potential was measured in situ . The sediments were composed of yellow, grey and black layers from the surface to depth. The spherical MMPs were concentrated near the grey‐black layer transition at a depth of 8–12 cm, while coccoid‐shaped magnetotactic bacteria near the yellow‐grey layer transition at a depth of 3–5 cm. The intertidal MMPs showed a deeper distribution at more reduced environments than coccoid‐shaped magnetotactic bacteria, and MMPs in lagoon sediments. Additionally the MMPs were concentrated significantly in layers with high proportion of fine sand and total organic carbon, rich in leachable iron but poor in nitrate. These results show an adaptation of spherical MMPs to the peculiar intertidal sediment habitat.

Changes in runout distances of debris flows over time in the Wenchuan earthquake zone - Shuai Zhang; Li-Min Zhang; Hong-Xin Chen; Quan Yuan; Hua Pan (Journal of Mountain Science, 2013)

Comparative transcriptome analysis of tobacco (Nicotiana tabacum) leaves to identify aroma compound-related genes expressed in different cultivated regions - Bo Lei; Xue-Hua Zhao; Kai Zhang; Jie Zhang; Wei Ren; Zhu Ren; Yi Chen; Hui-Na Zhao; Wen-Jie Pan; Wei Chen; Hong-Xun Li; Wen-Ya Deng; et al. (Molecular Biology Reports, 2013)

Antigenic and genetic characterization of a European avian-like H1N1 swine influenza virus from a boy in China in 2011 - Xian Qi; Lunbiao Cui; Yongjun Jiao; Yuning Pan; Xihan Li; Rongqiang Zu; Xiang Huo; Bin Wu; Fengyang Tang; Yongchun Song; Minghao Zhou; Hua Wang; et al. (Archives of Virology, 2013)

The isolation of Pi1, an allele at the Pik locus which confers broad spectrum resistance to rice blast - Lixia Hua; Jianzhong Wu; Caixia Chen; Weihuai Wu; Xiuying He; Fei Lin; Li Wang; Ikuo Ashikawa; Takashi Matsumoto; Ling Wang; Qinghua Pan (Theoretical and Applied Genetics, 2012)

Lipoxin A4 Inhibits 5-Lipoxygenase Translocation and Leukotrienes Biosynthesis to Exert a Neuroprotective Effect in Cerebral Ischemia/Reperfusion Injury - Le Wu; Sen Miao; Lin-Bing Zou; Ping Wu; Hua Hao; Ke Tang; Pan Zeng; Jing Xiong; Hong-Hua Li; Qiang Wu; Lei Cai; Du-Yun Ye (Journal of Molecular Neuroscience, 2012)

Frequency and characterization of porcine hokovirus (PHoV) in domestic pigs in eastern China - Yangyang Pan; Qiaoying Zeng; Caixia Zhu; Xiuguo Hua; Meng Wang; Kaixuan Pan; Li Cui (Archives of Virology, 2012)

Choline inhibits angiotensin II-induced cardiac hypertrophy by intracellular calcium signal and p38 MAPK pathway - Shu Wang; Hong-mei Han; Zhen-wei Pan; Peng-zhou Hang; Li-hua Sun; Ya-nan Jiang; Hao-xin Song; Zhi-min Du; Yan Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

Enzymatic fingerprints of polysaccharides of Dendrobium officinale and their application in identification of Dendrobium species - Xue-Qiang Zha; Li-Hua Pan; Jian-Ping Luo; Jun-Hui Wang; Peng Wei; Vibha Bansal (Journal of Natural Medicines, 2012)

SK channels modulate the excitability and firing precision of projection neurons in the robust nucleus of the arcopallium in adult male zebra finches - Guo-Qiang Hou; Xuan Pan; Cong-Shu Liao; Song-Hua Wang; Dong-Feng Li (Neuroscience Bulletin, 2012)

Polymorphisms in luteinizing hormone receptor and hypothalamic gonadotropin-releasing hormone genes and their effects on sperm quality traits in Chinese Holstein bulls - Li-Ping Sun; Qing-Zhi Du; Ya-Pan Song; Jun-Na Yu; Shu-Juan Wang; Lei Sang; Luo-Wen Song; Yao-Min Yue; Yu-Ze Lian; Sheng-Li Zhang; Guo-Hua Hua; Shu-Jun Zhang; et al. (Molecular Biology Reports, 2012)

The Group III Two-Component Histidine Kinase AlHK1 is Involved in Fungicides Resistance, Osmosensitivity, Spore Production and Impacts Negatively Pathogenicity in Alternaria longipes - Yi Yong Luo; Jin Kui Yang; Ming Liang Zhu; Chen Jian Liu; Hai Yan Li; Ze Bao Lu; Wen Zheng Pan; Zhong Hua Zhang; Wei Bi; Ke Qin Zhang (Current Microbiology, 2012)

Cloning and functional characterization of a caffeic acid O-methyltransferase from Trigonella foenum-graecum L - Jian-chun Qin; Ya-mei Zhang; Chen-yong Lang; Yan-hua Yao; Hong-yu Pan; Xiang Li (Molecular Biology Reports, 2012)

Bisphenol A exposure modifies methylation of imprinted genes in mouse oocytes via the estrogen receptor signaling pathway - Hu-He Chao; Xi-Feng Zhang; Bo Chen; Bo Pan; Lian-Jun Zhang; Lan Li; Xiao-Feng Sun; Qing-Hua Shi; Wei Shen (Histochemistry and Cell Biology, 2012)

Chemoresistance to Temozolomide in Human Glioma Cell Line U251 is Associated with Increased Activity of O 6-methylguanine-DNA Methyltransferase and Can be Overcome by Metronomic Temozolomide Regimen - Qiang Pan; Xue-jun Yang; Hua-min Wang; Xue-tao Dong; Wei Wang; Yu LI; Jing-min LI (Cell Biochemistry and Biophysics, 2012)

Prostaglandin I2 analogues suppress TNF-α expression in human monocytes via mitogen-activated protein kinase pathway - Wei-Li Wang; Chang-Hung Kuo; Yu-Te Chu; Ching-Hua Huang; Ka-Pan Lam; Shau-Ku Huang; Yuh-Jyh Jong; Yu-Ting Kuo; Chih-Hsing Hung (Inflammation Research, 2011)

Effects of palmitic acid on lipid metabolism homeostasis and apoptosis in goose primary hepatocytes - Zhixiong Pan; Jiwen Wang; Hui Tang; Liang Li; Jia Lv; Lu Xia; Chunchun Han; Feng Xu; Hua He; Hengyong Xu; Bo Kang (Molecular and Cellular Biochemistry, 2011)

osa-MIR393: a salinity- and alkaline stress-related microRNA gene - Peng Gao; Xi Bai; Liang Yang; Dekang Lv; Xin Pan; Yong Li; Hua Cai; Wei Ji; Qin Chen; Yanming Zhu (Molecular Biology Reports, 2011)

An ordered EST catalogue and gene expression profiles of cassava (Manihot esculenta) at key growth stages - You-Zhi Li; Ying-Hua Pan; Chang-Bin Sun; Hai-Tao Dong; Xing-Lu Luo; Zhi-Qiang Wang; Ji-Liang Tang; Baoshan Chen (Plant Molecular Biology, 2010)

Interleukin-10 gene polymorphisms in association with susceptibility to chronic hepatitis C virus infection: a meta-analysis study - Li-Zhou Zhang; Tian-Chen Zhang; Fa-Ming Pan; Zhen-Hua Zhang; Xu Li (Archives of Virology, 2010)

The Cucumber Lateral Suppressor Gene (CLS) Is Functionally Associated with Axillary Meristem Initiation - Li-Hua Yuan; Jun-Song Pan; Gang Wang; Jun Zhu; Wei-Wei Zhang; Zheng Li; Huan-Le He; Zhong-Nan Yang; Run Cai; Li-Huang Zhu (Plant Molecular Biology Reporter, 2010)

Post-conditioning protects cardiomyocytes from apoptosis via PKCε-interacting with calcium-sensing receptors to inhibit endo(sarco)plasmic reticulum–mitochondria crosstalk - Shiyun Dong; Zongyan Teng; Fang-hao Lu; Ya-jun Zhao; Hulun Li; Huan Ren; He Chen; Zhen-wei Pan; Yan-jie Lv; Bao-feng Yang; Ye Tian; Chang-qing Xu; et al. (Molecular and Cellular Biochemistry, 2010)

Gene expression profiles in the prefrontal cortex of SHR rats by cDNA microarrays - Jie Qiu; Qin Hong; Rong-hua Chen; Mei-ling Tong; Min Zhang; Li Fei; Xiao-qin Pan; Mei Guo; Xi-rong Guo; Xia Chi (Molecular Biology Reports, 2010)

Anti-α-actinin antibodies in relation to new-onset systemic lupus erythematosus and lupus nephritis - Wen-Hui Zhang; Hai-Feng Pan; Xue-Fei Zhao; Dong-Qing Ye; Xiang-Pei Li; Jian-Hua Xu (Molecular Biology Reports, 2010)

Profiling Gene Expression During Gland Morphogenesis of a Glanded and a Glandless Upland Cotton - Ying-Fan Cai; Min Chen; Quan Sun; Yong-Fang Xie; Sheng-Wei Li; Ming-Feng Jiang; Jian-Chuan Mo; You-Lu Yuan; Yu-Zhen Shi; Huai-Zhong Jiang; Zheng Pan; Yun-Ling Gao; et al. (Journal of Plant Biology, 2009)

Association study of a single nucleotide polymorphism in the exon 2 region of toll-like receptor 9 (TLR9) gene with susceptibility to systemic lupus erythematosus among Chinese - Chang-Juan Xu; Wen-Hui Zhang; Hai-Feng Pan; Xiang-Pei Li; Jian-Hua Xu; Dong-Qing Ye (Molecular Biology Reports, 2009)

Fas expression on peripheral blood lymphocytes in systemic lupus erythematosus: relation to the organ damage and lymphocytes apoptosis - Lian-Hong Li; Wen-Xian Li; Ou Wu; Guo-Qing Zhang; Hai-Feng Pan; Xiang-Pei Li; Jian-Hua Xu; Hong Dai; Dong-Qing Ye (Molecular Biology Reports, 2009)

Saponin fraction from Astragalus membranaceus roots protects mice against polymicrobial sepsis induced by cecal ligation and puncture by inhibiting inflammation and upregulating protein C pathway - Xing-hua Gao; Xian-xiang Xu; Rong Pan; Ying Li; Yu-bin Luo; Yu-feng Xia; Kazuya Murata; Hideaki Matsuda; Yue Dai (Journal of Natural Medicines, 2009)

Apolipoprotein E polymorphism in normal Han Chinese population: frequency and effect on lipid parameters - Shu Liang; Min Pan; Hai-Hua Geng; Hui Chen; Li-Qun Gu; Xiao-Tong Qin; Jin-Jun Qian; Jian-Hua Zhu; Chun-Feng Liu (Molecular Biology Reports, 2009)

FAS −1,377 G/A polymorphism is associated with cancer susceptibility: evidence from 10,564 cases and 12,075 controls - Li-Xin Qiu; Jian Shi; Hui Yuan; Xin Jiang; Kai Xue; Hai-Feng Pan; Jin Li; Ming-Hua Zheng (Human Genetics, 2009)

Gastric carcinoma with osteoclast-like giant cells: a case report and review of the literature - Li-duan Zheng; Xiu-ping Yang; Hua-xiong Pan; Xiu Nie; Jun He; Qing Lv; Qiang-song Tong (Journal of Zhejiang University-SCIENCE B, 2009)

Mechanism of Iodine Uptake by Cabbage: Effects of Iodine Species and Where It is Stored - Huan-Xin Weng; Chun-Lai Hong; Ai-Lan Yan; Le-Hua Pan; Ya-Chao Qin; Lü-Ting Bao; Ling-Li Xie (Biological Trace Element Research, 2008)

TM4SF3 promotes esophageal carcinoma metastasis via upregulating ADAM12m expression - Zhuan Zhou; Yu-Liang Ran; Hai Hu; Jian Pan; Zhi-Feng Li; Li-Zhao Chen; Li-Chao Sun; Liang Peng; Xi-Lu Zhao; Long Yu; Li-Xin Sun; Zhi-Hua Yang (Clinical & Experimental Metastasis, 2008)

Reduction in the in vitro expression of Brain–Pancreas Relative Protein by oxygen and glucose-deprivation - Yan-Hua Lin; Ai-Hua Liu; Yan Pan; Christel Westenbroek; Gert J Ter Horst; He-Ming Yu; Xue-Jun Li (Molecular and Cellular Biochemistry, 2007)

Characteristics of zonal anomaly of annual precipitation in the Northeastern China - Min-hua Yan; Wei Deng; Pan-qin Chen; Li-qiao Liang (Chinese Geographical Science, 2004)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)